Transfer film, method for producing laminate, and blocked isocyanate compound
A transfer film with a specific blocked isocyanate compound and refractive index adjusting layer addresses corrosion issues in touch panel electrode protective films, ensuring effective suppression of corrosion and reliable laminate production.
Patent Information
- Application Number
- JP2022526571
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-23
- Filing Date
- 2021-05-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-05-25
AI Technical Summary
Existing touch panel electrode protective films fail to adequately suppress corrosion of sensor electrodes and lead-out wiring, necessitating improved performance in this regard.
A transfer film with a photosensitive composition layer containing an alkali-soluble resin, a polymerizable compound, and a blocked isocyanate compound having an NCO value of 4.5 mmol/g or more, along with a refractive index adjusting layer, is used to form a protective film that suppresses corrosion by reacting with acid groups in the alkali-soluble resin during post-baking.
The transfer film effectively prevents corrosion of wiring and electrodes, enabling reliable manufacturing of laminates with enhanced protective properties.
Smart Images

Figure 0007607654000034 
Figure 0007607654000035 
Figure 0007607654000036
Abstract
Description
[Technical field]
[0001] The present invention relates to a transfer film, a method for producing a laminate, and a blocked isocyanate compound. [Background technology]
[0002] Because the number of steps required to obtain a desired pattern is small, a method in which a photosensitive composition layer is provided on a substrate using a transfer film, exposed through a mask, and then developed is widely used. A transfer film having a photosensitive composition layer may be used to form a protective film (touch panel electrode protective film) for protecting a sensor electrode and an extraction wiring in a touch panel. For example, Patent Document 1 discloses a photosensitive resin film (photosensitive composition layer) containing an alkali-soluble resin, a polymerizable compound having an unsaturated double bond, a photopolymerization initiator, a coloring material, and a blocked isocyanate compound as a thermal crosslinking agent. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-071372 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, there has been a demand for further improvement in the performance of touch panel electrode protective films. Specifically, there is a demand for touch panel electrode protective films that can suppress corrosion of sensor electrodes and lead wiring in touch panels. The present inventors used a transfer film having a photosensitive composition layer as described in Patent Document 1 to form a touch panel electrode protective film, and found that depending on the type of blocked isocyanate compound contained in the photosensitive composition layer, corrosion of wiring and electrodes may not be suppressed, indicating that there is room for improvement.
[0005] Therefore, an object of the present invention is to provide a transfer film capable of suppressing corrosion of wiring and electrodes. Another object of the present invention is to provide a method for producing a laminate using the transfer film. Another object of the present invention is to provide a novel blocked isocyanate compound. [Means for solving the problem]
[0006] As a result of extensive investigation into the above problems, the present inventors have found that the above problems can be solved by the following configuration.
[0007] [1] A temporary support and a photosensitive composition layer disposed on the temporary support, The photosensitive composition layer of the transfer film comprises an alkali-soluble resin, a polymerizable compound, a polymerization initiator, and a blocked isocyanate compound having an NCO value of 4.5 mmol / g or more. [2] The transfer film according to [1], wherein the NCO value of the blocked isocyanate compound is greater than 5.0 mmol / g. [3] The transfer film according to [1] or [2], wherein the blocked isocyanate compound has a ring structure. [4] The transfer film according to any one of [1] to [3], wherein the blocked isocyanate compound is a blocked isocyanate compound represented by formula Q. B 1 -A 1 -L 1 -A 2 -B 2 formula Q In formula Q, B 1 and B. 2 each independently represents a blocked isocyanate group, A 1 and A 2 each independently represents a single bond or an alkylene group having 1 to 10 carbon atoms; L 1 represents a divalent linking group. [5] The transfer film according to any one of [1] to [4], wherein the blocked isocyanate compound is a blocked isocyanate compound represented by the formula QA. B 1a -A 1a -L 1a -A 2a -B 2a QA In the QA section, B 1a and B. 2a each independently represents a blocked isocyanate group, A 1a and A 2a each independently represents a divalent linking group; L 1a represents a cyclic divalent saturated hydrocarbon group or a divalent aromatic hydrocarbon group. [6] The transfer film according to any one of [1] to [5], wherein the photosensitive composition layer further contains a blocked isocyanate compound having an NCO value of less than 4.5 mmol / g. [7] the alkali-soluble resin contains a structural unit derived from a vinylbenzene derivative, a structural unit having a radical polymerizable group, and a structural unit having an acid group, The transfer film according to any one of [1] to [6], wherein the content of the structural unit derived from the vinylbenzene derivative is 35 mass % or more based on the total amount of all structural units contained in the alkali-soluble resin. [8] The transfer film according to [7], wherein the content of the structural unit derived from the vinylbenzene derivative is 45 mass% or more based on the total amount of all structural units contained in the alkali-soluble resin. [9] Further comprising a refractive index adjustment layer, the refractive index adjusting layer is disposed in contact with the photosensitive composition layer, The transfer film according to any one of [1] to [8], wherein the refractive index adjusting layer has a refractive index of 1.60 or more.
[10] The transfer film according to any one of [1] to [9], wherein the photosensitive composition layer is used for forming a protective film for a touch panel electrode.
[11] a lamination step of contacting and laminating the photosensitive composition layer on the temporary support of the transfer film according to any one of [1] to
[10] with a substrate having a conductive layer to obtain a substrate with a photosensitive composition layer having the substrate, the conductive layer, the photosensitive composition layer, and the temporary support in this order; an exposure step of pattern-exposing the photosensitive composition layer; A development step of developing the exposed photosensitive composition layer to form a pattern, The method for producing a laminate further comprises a peeling step of peeling the temporary support from the substrate with the photosensitive composition layer between the laminating step and the exposure step, or between the exposure step and the development step.
[12] A temporary support and a photosensitive composition layer disposed on the temporary support, the photosensitive composition layer contains an alkali-soluble resin, a polymerizable compound, a polymerization initiator, and a blocked isocyanate compound; A transfer film, wherein the NCO value of the photosensitive composition layer is greater than 0.50 mmol / g.
[13] A blocked isocyanate compound represented by the formula QA. B 1a -A 1a -L 1a -A 2a -B 2a QA In the QA section, B 1a and B. 2a each independently represents a blocked isocyanate group, A 1a and A 2a each independently represents a divalent linking group; L 1a represents a cyclic divalent saturated hydrocarbon group or a divalent aromatic hydrocarbon group.
[14] The blocked isocyanate compound according to
[13] , which is represented by the formula Q-1 described below.
[15] The blocked isocyanate compound according to
[14] , wherein the mass ratio of cis isomer to trans isomer is cis / trans isomer=10 / 90 to 90 / 10. Effect of the Invention
[0008] According to the present invention, a transfer film capable of suppressing corrosion of wiring and electrodes can be provided. In addition, according to the present invention, a method for producing a laminate using the transfer film can be provided. In addition, the present invention can also provide a novel blocked isocyanate compound. [Brief description of the drawings]
[0009] [Figure 1] 1 is a schematic cross-sectional view showing a specific example of a touch panel to which the transfer film of the present invention can be applied. [Diagram 2] 1 is a schematic cross-sectional view showing a specific example of a touch panel to which the transfer film of the present invention can be applied. [Diagram 3] 1 is a schematic plan view showing a specific example of a touch panel to which the transfer film of the present invention can be applied. [Figure 4] FIG. 4 is a cross-sectional view taken along line AA in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described in detail below. In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits. In addition, in the numerical ranges described in this specification, the upper limit or lower limit described in a certain numerical range may be replaced with the upper limit or lower limit of another numerical range described in a certain numerical range. In addition, in the numerical ranges described in this specification, the upper limit or lower limit described in a certain numerical range may be replaced with a value shown in the examples.
[0011] In addition, the term "process" in this specification includes not only an independent process but also a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved.
[0012] In this specification, the term "transparent" means that the average transmittance of visible light with a wavelength of 400 to 700 nm is 80% or more, and preferably 90% or more. The average transmittance of visible light is a value measured using a spectrophotometer, and can be measured using, for example, a spectrophotometer U-3310 manufactured by Hitachi, Ltd.
[0013] In the present disclosure, unless otherwise specified, the weight average molecular weight (Mw) and number average molecular weight (Mn) are molecular weights measured using a gel permeation chromatography (GPC) analyzer equipped with columns of TSKgel GMHxL, TSKgel G4000HxL, or TSKgel G2000HxL (all of which are product names manufactured by Tosoh Corporation), detected with a differential refractometer in THF (tetrahydrofuran), and converted using polystyrene as a standard substance. In the present disclosure, unless otherwise specified, the molecular weight of a compound having a molecular weight distribution is the weight average molecular weight. In this specification, unless otherwise specified, the refractive index is a value measured by an ellipsometer at a wavelength of 550 nm.
[0014] In this specification, "(meth)acrylic" is a concept that includes both acrylic and methacrylic, "(meth)acrylate" is a concept that includes both acrylate and methacrylate, and "(meth)acryloxy group" is a concept that includes both acryloxy group and methacryloxy group.
[0015] [First embodiment of transfer film] The transfer film in the first embodiment of the present invention (hereinafter also referred to as "first transfer film") has a temporary support and a photosensitive composition layer disposed on the temporary support, and the photosensitive composition layer contains an alkali-soluble resin, a polymerizable compound, a polymerization initiator, and a blocked isocyanate compound having an NCO value of 4.5 mmol / g or more. Hereinafter, the blocked isocyanate compound having an NCO value of 4.5 mmol / g or more is also referred to as "first blocked isocyanate compound."
[0016] A characteristic feature of the first transfer film is that the photosensitive composition layer of the first transfer film contains a first blocked isocyanate compound. Here, an example of a method for forming a protective film using the first transfer film is to contact and bond the first transfer film to a substrate having a conductive layer (such as a sensor electrode and lead-out wiring), and then to form a patterned protective film through processes such as pattern exposure, development, and post-baking of the photosensitive composition layer of the first transfer film. The inventors have discovered that the alkali-soluble resin contained in the photosensitive composition layer is necessary in terms of the developability of the photosensitive composition layer, but that the action of acid groups such as carboxy groups contained in the alkali-soluble resin can cause corrosion of the conductive layer. To address this problem, the present inventors have discovered that the use of a first blocked isocyanate compound can suppress corrosion of the conductive layer. The reason for this is presumably that the post-bake step generates a sufficient amount of isocyanate groups from the blocked isocyanate compound to react with the acid groups of the alkali-soluble resin, thereby suppressing corrosion of the conductive layer.
[0017] Hereinafter, each member constituting the first transfer film will be described.
[0018] <Temporary support> The first transfer film has a temporary support, which is a member that supports the photosensitive composition layer and other components described below, and is ultimately removed by a peeling treatment. The temporary support is preferably a film, more preferably a resin film. As the temporary support, a film having flexibility and not significantly deforming, shrinking, or stretching under pressure or under pressure and heat can be used. Such films include polyethylene terephthalate films (eg, biaxially oriented polyethylene terephthalate films), cellulose triacetate films, polystyrene films, polyimide films, and polycarbonate films. Among these, the temporary support is preferably a biaxially oriented polyethylene terephthalate film. Moreover, it is preferable that the film used as the temporary support is free from deformation such as wrinkles and scratches.
[0019] The temporary support preferably has high transparency so that pattern exposure can be performed through the temporary support, and the transmittance at 365 nm is preferably 60% or more, more preferably 70% or more. From the viewpoints of pattern formability during pattern exposure through the temporary support and transparency of the temporary support, it is preferable that the haze of the temporary support is small. Specifically, the haze value of the temporary support is preferably 2% or less, more preferably 0.5% or less, and even more preferably 0.1% or less. From the viewpoints of pattern formability during pattern exposure through the temporary support and transparency of the temporary support, it is preferable that the number of fine particles, foreign matter and defects contained in the temporary support is small. The number of fine particles, foreign matter and defects with a diameter of 1 μm or more is 50 / 10 mm 2 Less than 10 pieces / 10mm is preferable. 2 Less than 3 pieces / 10mm is more preferable. 2 Less than 0 / 10mm is more preferable. 2 is particularly preferred.
[0020] The thickness of the temporary support is not particularly limited, but is preferably from 5 to 200 μm, and from the viewpoints of ease of handling and versatility, is more preferably from 10 to 150 μm, and further preferably from 10 to 50 μm.
[0021] A layer containing fine particles (lubricant layer) may be provided on the surface of the temporary support in order to provide handling properties. The lubricant layer may be provided on one side or both sides of the temporary support. The diameter of the particles contained in the lubricant layer may be 0.05 to 0.8 μm. The thickness of the lubricant layer may be 0.05 to 1.0 μm.
[0022] Examples of the temporary support include a biaxially oriented polyethylene terephthalate film having a thickness of 16 μm, a biaxially oriented polyethylene terephthalate film having a thickness of 12 μm, and a biaxially oriented polyethylene terephthalate film having a thickness of 9 μm.
[0023] Preferred forms of the temporary support are described, for example, in paragraphs
[0017] to
[0018] of JP 2014-085643 A, paragraphs
[0019] to
[0026] of JP 2016-027363 A, paragraphs
[0041] to
[0057] of WO 2012 / 081680 A, and paragraphs
[0029] to
[0040] of WO 2018 / 179370 A, the contents of which are incorporated herein by reference.
[0024] <Photosensitive composition layer> The first transfer film has a photosensitive composition layer. After the photosensitive composition layer is transferred onto an object to be transferred, the photosensitive composition layer is exposed to light and developed, thereby forming a pattern on the object to be transferred. The photosensitive composition layer contains an alkali-soluble resin, a polymerizable compound, a polymerization initiator, and a first blocked isocyanate compound. The photosensitive composition layer may be either a positive type or a negative type. The positive-type photosensitive composition layer is a photosensitive composition layer in which the exposed portion becomes more soluble in a developer upon exposure, and the negative-type photosensitive composition layer is a photosensitive composition layer in which the exposed portion becomes less soluble in a developer upon exposure. Among them, it is preferable to use a negative photosensitive composition layer. When the photosensitive composition layer is a negative photosensitive composition layer, the formed pattern corresponds to a cured film. The components contained in the negative photosensitive composition layer will be described in detail below.
[0025] [Polymerizable compound] The photosensitive composition layer contains a polymerizable compound. The polymerizable compound is a compound having a polymerizable group. Examples of the polymerizable group include a radically polymerizable group and a cationic polymerizable group, and the radically polymerizable group is preferred.
[0026] The polymerizable compound preferably contains a radically polymerizable compound having an ethylenically unsaturated group (hereinafter, also simply referred to as an "ethylenically unsaturated compound"). The ethylenically unsaturated group is preferably a (meth)acryloxy group.
[0027] The ethylenically unsaturated compound preferably includes a di- or higher functional ethylenically unsaturated compound. Here, the term "di- or higher functional ethylenically unsaturated compound" refers to a compound having two or more ethylenically unsaturated groups in one molecule.
[0028] As the ethylenically unsaturated compound, a (meth)acrylate compound is preferred. The ethylenically unsaturated compound preferably contains a difunctional ethylenically unsaturated compound (preferably a difunctional (meth)acrylate compound) and a tri- or higher functional ethylenically unsaturated compound (preferably a tri- or higher functional (meth)acrylate compound), for example, from the viewpoint of film strength after curing.
[0029] Examples of the difunctional ethylenically unsaturated compound include tricyclodecane dimethanol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate.
[0030] Commercially available bifunctional ethylenically unsaturated compounds include, for example, tricyclodecane dimethanol diacrylate (trade name: NK Ester A-DCP, Shin-Nakamura Chemical Co., Ltd.), tricyclodecane dimethanol dimethacrylate (trade name: NK Ester DCP, Shin-Nakamura Chemical Co., Ltd.), 1,9-nonanediol diacrylate (trade name: NK Ester A-NOD-N, Shin-Nakamura Chemical Co., Ltd.), 1,10-decanediol diacrylate (trade name: NK Ester A-DOD-N, Shin-Nakamura Chemical Co., Ltd.), and 1,6-hexanediol diacrylate (trade name: NK Ester A-HD-N, Shin-Nakamura Chemical Co., Ltd.).
[0031] Examples of tri- or higher functional ethylenically unsaturated compounds include dipentaerythritol (tri / tetra / penta / hexa)(meth)acrylate, pentaerythritol (tri / tetra)(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, isocyanuric acid (meth)acrylate, and glycerin tri(meth)acrylate.
[0032] Here, "(tri / tetra / penta / hexa)(meth)acrylate" is a concept that includes tri(meth)acrylate, tetra(meth)acrylate, penta(meth)acrylate, and hexa(meth)acrylate. Also, "(tri / tetra)(meth)acrylate" is a concept that includes tri(meth)acrylate and tetra(meth)acrylate. For the tri- or higher functional ethylenically unsaturated compound, there is no particular upper limit on the number of functional groups, but it can be, for example, 20 or less functional groups, or 15 or less functional groups.
[0033] An example of a commercially available tri- or higher functional ethylenically unsaturated compound is dipentaerythritol hexaacrylate (trade name: KAYARAD DPHA, Shin-Nakamura Chemical Co., Ltd.).
[0034] More preferably, the ethylenically unsaturated compound includes 1,9-nonanediol di(meth)acrylate or 1,10-decanediol di(meth)acrylate, and dipentaerythritol (tri / tetra / penta / hexa)(meth)acrylate.
[0035] Examples of the ethylenically unsaturated compound include caprolactone-modified (meth)acrylate compounds (KAYARAD (registered trademark) DPCA-20 from Nippon Kayaku Co., Ltd., A-9300-1CL from Shin-Nakamura Chemical Co., Ltd., etc.), alkylene oxide-modified (meth)acrylate compounds (KAYARAD (registered trademark) RP-1040 from Nippon Kayaku Co., Ltd., ATM-35E and A-9300 from Shin-Nakamura Chemical Co., Ltd., EBECRYL (registered trademark) 135 from Daicel-Allnex Corporation, etc.), and ethoxylated glycerin triacrylate (NK Ester A-GLY-9E from Shin-Nakamura Chemical Co., Ltd., etc.).
[0036] The ethylenically unsaturated compound may also include a urethane (meth)acrylate compound. The urethane (meth)acrylate compound is preferably a trifunctional or higher urethane (meth)acrylate compound. Examples of the trifunctional or higher urethane (meth)acrylate compound include 8UX-015A (Taisei Fine Chemical Co., Ltd.), NK Ester UA-32P (Shin-Nakamura Chemical Co., Ltd.), and NK Ester UA-1100H (Shin-Nakamura Chemical Co., Ltd.).
[0037] From the viewpoint of improving developability, the ethylenically unsaturated compound preferably contains an ethylenically unsaturated compound having an acid group.
[0038] Examples of the acid group include a phosphoric acid group, a sulfonic acid group, and a carboxy group. Among these, the carboxy group is preferred as the acid group.
[0039] Examples of the ethylenically unsaturated compound having an acid group include a tri- or tetrafunctional ethylenically unsaturated compound having an acid group [a compound having a carboxy group introduced into a pentaerythritol tri- or tetraacrylate (PETA) skeleton (acid value: 80 to 120 mg KOH / g)] and a penta- or hexafunctional ethylenically unsaturated compound having an acid group (a compound having a carboxy group introduced into a dipentaerythritol penta- or hexaacrylate (DPHA) skeleton (acid value: 25 to 70 mg KOH / g)]. The tri- or higher functional ethylenically unsaturated compound having an acid group may be used in combination with a bifunctional ethylenically unsaturated compound having an acid group, if necessary.
[0040] The ethylenically unsaturated compound having an acid group is preferably at least one compound selected from the group consisting of ethylenically unsaturated compounds having two or more functional groups and having a carboxy group, and carboxylic anhydrides thereof. When the ethylenically unsaturated compound having an acid group is at least one compound selected from the group consisting of ethylenically unsaturated compounds having two or more functional groups and having a carboxy group, and carboxylic anhydrides thereof, the developability and film strength are further improved.
[0041] Examples of difunctional or higher functional ethylenically unsaturated compounds having a carboxy group include ARONIX (registered trademark) TO-2349 (Toagosei Co., Ltd.), ARONIX (registered trademark) M-520 (Toagosei Co., Ltd.), and ARONIX (registered trademark) M-510 (Toagosei Co., Ltd.).
[0042] As the ethylenically unsaturated compound having an acid group, the polymerizable compounds having an acid group described in paragraphs
[0025] to
[0030] of JP-A-2004-239942 can be preferably used, and the contents of this publication are incorporated herein by reference.
[0043] The molecular weight of the ethylenically unsaturated compound is preferably from 200 to 3,000, more preferably from 250 to 2,600, further preferably from 280 to 2,200, and particularly preferably from 300 to 2,200.
[0044] Among the ethylenically unsaturated compounds, the content of ethylenically unsaturated compounds having a molecular weight of 300 or less is preferably 30 mass % or less, more preferably 25 mass % or less, and even more preferably 20 mass % or less, based on the content of all ethylenically unsaturated compounds contained in the photosensitive composition layer.
[0045] The photosensitive composition layer may contain one kind of polymerizable compound alone, or may contain two or more kinds of polymerizable compounds.
[0046] The content of the polymerizable compound (preferably an ethylenically unsaturated compound) is preferably 1 to 70 mass %, more preferably 10 to 70 mass %, further preferably 20 to 60 mass %, and particularly preferably 20 to 50 mass %, relative to the total mass of the photosensitive composition layer.
[0047] When the photosensitive composition layer contains a di- or higher functional ethylenically unsaturated compound, it may further contain a monofunctional ethylenically unsaturated compound.
[0048] When the photosensitive composition layer contains a difunctional or higher functional ethylenically unsaturated compound, the difunctional or higher functional ethylenically unsaturated compound is preferably a major component in the ethylenically unsaturated compounds contained in the photosensitive composition layer.
[0049] When the photosensitive composition layer contains a difunctional or higher ethylenically unsaturated compound, the content of the difunctional or higher ethylenically unsaturated compound is preferably 60 to 100 mass%, more preferably 80 to 100 mass%, and even more preferably 90 to 100 mass%, based on the content of all ethylenically unsaturated compounds contained in the photosensitive composition layer.
[0050] When the photosensitive composition layer contains an ethylenically unsaturated compound having an acid group (preferably, a di- or higher functional ethylenically unsaturated compound having a carboxy group or a carboxylic acid anhydride thereof), the content of the ethylenically unsaturated compound having an acid group is preferably 1 to 50 mass %, more preferably 1 to 20 mass %, and even more preferably 1 to 10 mass %, relative to the total mass of the photosensitive composition layer.
[0051] [Polymerization initiator] The photosensitive composition layer contains a polymerization initiator. The polymerization initiator is preferably a photopolymerization initiator. Examples of the photopolymerization initiator include a photopolymerization initiator having an oxime ester structure (hereinafter also referred to as an "oxime-based photopolymerization initiator"), a photopolymerization initiator having an α-aminoalkylphenone structure (hereinafter also referred to as an "α-aminoalkylphenone-based photopolymerization initiator"), a photopolymerization initiator having an α-hydroxyalkylphenone structure (hereinafter also referred to as an "α-hydroxyalkylphenone-based polymerization initiator"), a photopolymerization initiator having an acylphosphine oxide structure (hereinafter also referred to as an "acylphosphine oxide-based photopolymerization initiator"), and a photopolymerization initiator having an N-phenylglycine structure (hereinafter also referred to as an "N-phenylglycine-based photopolymerization initiator").
[0052] The photopolymerization initiator preferably contains at least one selected from the group consisting of oxime-based photopolymerization initiators, α-aminoalkylphenone-based photopolymerization initiators, α-hydroxyalkylphenone-based polymerization initiators, and N-phenylglycine-based photopolymerization initiators, and more preferably contains at least one selected from the group consisting of oxime-based photopolymerization initiators, α-aminoalkylphenone-based photopolymerization initiators, and N-phenylglycine-based photopolymerization initiators.
[0053] In addition, as the photopolymerization initiator, for example, the polymerization initiators described in paragraphs
[0031] to
[0042] of JP2011-095716A and paragraphs
[0064] to
[0081] of JP2015-014783A may be used.
[0054] Examples of commercially available photopolymerization initiators include 1-[4-(phenylthio)]phenyl-1,2-octanedione-2-(O-benzoyloxime) [trade name: IRGACURE (registered trademark) OXE-01, manufactured by BASF], 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone-1-(O-acetyloxime) [trade name: IRGACURE (registered trademark) OXE-02, manufactured by BASF], 8-[5-(2,4,6-trimethylphenyl)-11-(2-ethylhexyl)-11H-benzo[a]carbazolyl][2-(2,2,3,3-tetrafluoropropoxy)phenyl]methanone-(O-acetyloxime) [trade name: IRGACURE (registered trademark) OXE-03, manufactured by BASF], 1-[4-[4-(2-benzofuranylcarbonyl)phenyl]thio]phenyl]-4-methyl-1-pentanone-1-(O-acetyloxime) [trade name: IRGACURE (registered trademark) OXE-04, manufactured by BASF], 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone [trade name: IRGACURE (registered trademark) 379EG, manufactured by BASF], 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one [trade name: IRGACURE (registered trademark) 907, manufactured by BASF], 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)benzyl]phenyl}-2-methylpropan-1-one [trade name: IRGACURE (registered trademark) 127, manufactured by BASF], 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1 [trade name: IRGACURE® 369, manufactured by BASF], 2-hydroxy-2-methyl-1-phenyl-propan-1-one [trade name: IRGACURE® 1173, manufactured by BASF], 1-hydroxycyclohexyl phenyl ketone [trade name: IRGACURE® 184, manufactured by BASF], 2,2-dimethoxy-1,2-Diphenylethan-1-one (trade name: IRGACURE 651, manufactured by BASF), oxime ester compound (trade name: Lunar (registered trademark) 6, manufactured by DKSH Japan Co., Ltd.), 1-[4-(phenylthio)phenyl]-3-cyclopentylpropane-1,2-dione-2-(O-benzoyloxime) (trade name: TR-PBG-305, manufactured by Changzhou Strong Electronic New Materials Co., Ltd.), 1,2-propanedione, 3-cyclohexyl-1-[9-ethyl-6-(2-furanylcarbonyl)-9H-carbazol-3-yl]-, 2-(O-acetyloxime) (trade name: TR-PBG- 326, Changzhou Strong Electronic New Materials Co., Ltd.), 3-cyclohexyl-1-(6-(2-(benzoyloxyimino)hexanoyl)-9-ethyl-9H-carbazol-3-yl)-propane-1,2-dione-2-(O-benzoyloxime) (trade name: TR-PBG-391, Changzhou Strong Electronic New Materials Co., Ltd.), and APi-307 (1-(biphenyl-4-yl)-2-methyl-2-morpholinopropan-1-one, Shenzhen UV-ChemTech Ltd.).
[0055] The photosensitive composition layer may contain one type of photopolymerization initiator alone, or may contain two or more types of photopolymerization initiators.
[0056] The content of the photopolymerization initiator is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, based on the total mass of the photosensitive composition layer, and the upper limit of the content of the photopolymerization initiator is preferably 10% by mass or less, more preferably 5% by mass or less, based on the total mass of the photosensitive composition layer.
[0057] [Alkali-soluble resin] The photosensitive composition layer contains an alkali-soluble resin, and when the photosensitive composition layer contains an alkali-soluble resin, the solubility of the photosensitive composition layer (non-exposed area) in a developer is improved.
[0058] In the present disclosure, the term "alkali-soluble" refers to a dissolution rate determined by the following method of 0.01 μm / sec or more. A propylene glycol monomethyl ether acetate solution containing a target compound (e.g., a resin) at a concentration of 25% by mass is applied onto a glass substrate, and then heated in an oven at 100° C. for 3 minutes to form a coating film (thickness 2.0 μm) of the target compound. The coating film is immersed in a 1% by mass aqueous solution of sodium carbonate (liquid temperature 30° C.) to determine the dissolution rate (μm / sec) of the coating film. If the target compound is not soluble in propylene glycol monomethyl ether acetate, the target compound is dissolved in an organic solvent having a boiling point of less than 200° C. other than propylene glycol monomethyl ether acetate (for example, tetrahydrofuran, toluene, or ethanol).
[0059] The alkali-soluble resin preferably contains a structural unit derived from a vinylbenzene derivative, a structural unit having a radically polymerizable group, and a structural unit having an acid group.
[0060] (Structural unit derived from vinylbenzene derivatives) As the structural unit derived from a vinylbenzene derivative (hereinafter also referred to as a "vinylbenzene derivative unit"), a unit represented by the following formula (1) (hereinafter also referred to as a "unit (1)") is preferable.
[0061] [ka]
[0062] In formula (1), n represents an integer of 0 to 5. 1 represents a substituent. When n is 2 or more, two R 1 may be bonded to each other to form a condensed ring structure. 1 may be the same or different.
[0063] R 1 The substituent represented by the formula (I) is preferably a halogen atom, an alkyl group, an aryl group, an alkoxy group, or a hydroxyl group.
[0064] R 1As the halogen atom, which is one of the preferred embodiments, a fluorine atom, a chlorine atom, a bromine atom or an iodine atom is preferred, and a fluorine atom, a chlorine atom or a bromine atom is more preferred. R 1 The alkyl group, which is one of the preferred embodiments, preferably has 1 to 20 carbon atoms, more preferably 1 to 12, still more preferably 1 to 6, still more preferably 1 to 3, particularly preferably 1 or 2, and most preferably 1. R 1 The aryl group, which is one of the preferred embodiments, preferably has 6 to 20 carbon atoms, more preferably 6 to 12 carbon atoms, further preferably 6 to 10 carbon atoms, and particularly preferably 6 carbon atoms. R 1 The number of carbon atoms in the alkoxy group, which is one of the preferred embodiments, is preferably 1 to 20, more preferably 1 to 12, more preferably 1 to 6, even more preferably 1 to 3, particularly preferably 1 or 2, and most preferably 1.
[0065] R 11 represents a hydrogen atom or a methyl group.
[0066] In the formula (1), n is particularly preferably an integer of 0 to 2. In formula (1), when n is 2, two R 1 The condensed ring structure that can be formed by bonding to each other is preferably a naphthalene ring structure or an anthracene ring structure.
[0067] Examples of monomers for forming the vinylbenzene derivative unit include styrene, 1-vinylnaphthalene, 2-vinylnaphthalene, vinylbiphenyl, vinylanthracene, 4-hydroxystyrene, 4-bromostyrene, 4-methoxystyrene, and α-methylstyrene, with styrene being particularly preferred.
[0068] The content of the vinylbenzene derivative unit is preferably 30% by mass or more, more preferably 40% by mass or more, and even more preferably 45% by mass or more, relative to the total amount of all structural units contained in the alkali-soluble resin, since the effects of the present invention are more excellent. The upper limit of the content of the vinylbenzene derivative unit is preferably 70% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less.
[0069] The alkali-soluble resin may contain one type of vinylbenzene derivative unit alone, or may contain two or more types of vinylbenzene derivative units.
[0070] In the present disclosure, when the content of a "structural unit" is specified in mass %, unless otherwise specified, the "structural unit" is synonymous with the "monomer unit." Furthermore, in the present disclosure, when a resin or polymer has two or more specific structural units, the content of the specific structural units represents the total content of the two or more specific structural units, unless otherwise specified.
[0071] (Structural unit having a radically polymerizable group) In the structural unit having a radically polymerizable group (hereinafter also referred to as a "radical polymerizable group-containing unit"), the radically polymerizable group is preferably a group having an ethylenic double bond (hereinafter also referred to as an "ethylenically unsaturated group"), and more preferably a (meth)acryloyl group.
[0072] As the radically polymerizable group-containing unit, a unit represented by the following formula (2) (hereinafter also referred to as "unit (2)") is preferable.
[0073] [ka]
[0074] In formula (2), R 2 and R 3 each independently represents a hydrogen atom or an alkyl group, and L represents a divalent linking group.
[0075] R 2 and R 3 The number of carbon atoms in the alkyl group represented by the following formula (1) is preferably 1 to 3, more preferably 1 or 2, and further preferably 1.
[0076] The divalent linking group represented by L is preferably one group selected from the group consisting of a carbonyl group (i.e., a -C(=O)- group), an oxygen atom (i.e., a -O- group), an alkylene group, and an arylene group, or a group formed by linking two or more groups selected from the above group. The alkylene group or arylene group may each be substituted with a substituent (for example, a hydroxyl group other than a primary hydroxyl group, a halogen atom, etc.). The divalent linking group represented by L may have a branched structure.
[0077] The divalent linking group represented by L preferably has 1 to 30 carbon atoms, more preferably 1 to 20 carbon atoms, and even more preferably 2 to 10 carbon atoms.
[0078] As the divalent linking group represented by L, the groups shown below are particularly preferred.
[0079] [ka]
[0080] In each of the above groups, *1 represents the bonding position to a carbon atom contained in the main chain in formula (2), and *2 represents the bonding position to a carbon atom forming a double bond in formula (2). In (L-5), n and m each independently represent an integer of 1 to 6.
[0081] Examples of the radically polymerizable group-containing unit include a structural unit in which an epoxy group-containing monomer is added to a (meth)acrylic acid unit, and a structural unit in which an isocyanate group-containing monomer is added to a hydroxyl group-containing monomer unit. The epoxy group-containing monomer is preferably an epoxy group-containing (meth)acrylate having a total carbon number of 5 to 24, more preferably an epoxy group-containing (meth)acrylate having a total carbon number of 5 to 12, and even more preferably glycidyl (meth)acrylate or 3,4-epoxycyclohexylmethyl (meth)acrylate. The hydroxyl group-containing monomer for forming the hydroxyl group-containing monomer unit is preferably a hydroxyalkyl(meth)acrylate having a total of 4 to 24 carbon atoms, more preferably a hydroxyalkyl(meth)acrylate having a total of 4 to 12 carbon atoms, and more preferably a hydroxyethyl(meth)acrylate having a total of 4 to 12 carbon atoms. p) Acrylate is more preferred.
[0082] Here, the term "(meth)acrylic acid unit" refers to a structural unit derived from (meth)acrylic acid. Similarly, in this specification, a term in which the word "unit" is added immediately after the name of a monomer (for example, "hydroxyl group-containing monomer unit") means a structural unit derived from that monomer (for example, a hydroxyl group-containing monomer).
[0083] More specifically, the radical polymerizable group-containing unit is A structural unit in which glycidyl (meth)acrylate is added to a (meth)acrylic acid unit, A structural unit in which (meth)acrylic acid is added to a (meth)acrylic acid unit, A structural unit in which 3,4-epoxycyclohexylmethyl (meth)acrylate is added to a (meth)acrylic acid unit. A structural unit in which 2-isocyanatoethyl (meth)acrylate is added to a hydroxyethyl (meth)acrylate unit, A structural unit in which 2-isocyanatoethyl (meth)acrylate is added to a hydroxybutyl (meth)acrylate unit, A structural unit in which 2-isocyanatoethyl (meth)acrylate is added to a hydroxystyrene unit, and the like.
[0084] Examples of the radical polymerizable group-containing unit include A structural unit in which glycidyl (meth)acrylate is added to a (meth)acrylic acid unit or a structural unit in which 3,4-epoxycyclohexylmethyl (meth)acrylate is added to a (meth)acrylic acid unit is more preferred. A structural unit in which glycidyl methacrylate is added to a methacrylic acid unit or a structural unit in which 3,4-epoxycyclohexylmethyl methacrylate is added to a methacrylic acid unit is particularly preferred.
[0085] The content of the radically polymerizable group-containing unit is preferably 20 to 50 mass%, more preferably 25 to 45 mass%, and even more preferably 30 to 40 mass%, based on the total amount of all structural units contained in the alkali-soluble resin, in order to obtain better effects of the present invention.
[0086] The alkali-soluble resin may contain one type of radically polymerizable group-containing unit alone, or may contain two or more types of radically polymerizable group-containing units.
[0087] (Structural unit having an acid group) When the alkali-soluble resin contains a structural unit having an acid group (hereinafter also referred to as an "acid group-containing unit"), the photosensitive composition layer has alkali solubility.
[0088] Examples of the acid group in the acid group-containing unit include a carboxy group, a sulfonic acid group, a sulfate group, and a phosphate group, with the carboxy group being preferred.
[0089] As the acid group-containing unit, a unit represented by the following formula (3) (hereinafter also referred to as "unit (3)") is preferable.
[0090] [ka]
[0091] In formula (3), R 5 represents a hydrogen atom or an alkyl group.
[0092] R 5 The alkyl group represented by the following formula (I) preferably has 1 to 3 carbon atoms, more preferably 1 or 2, and even more preferably 1. R 5is preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, more preferably a hydrogen atom, a methyl group, or an ethyl group, and even more preferably a hydrogen atom or a methyl group.
[0093] As a monomer for forming the acid group-containing unit, (meth)acrylic acid is particularly preferred.
[0094] The content of the acid group-containing unit is preferably 5 to 30 mass%, more preferably 10 to 25 mass%, and even more preferably 15 to 20 mass%, based on the total amount of all structural units contained in the alkali-soluble resin, in order to obtain better effects of the present invention.
[0095] The alkali-soluble resin may contain a single type of acid group-containing unit, or may contain two or more types of acid group-containing units.
[0096] (Other structural units) The alkali-soluble resin may contain structural units other than the above-mentioned structural units. Other structural units include alkyl(meth)acrylate structural units having a hydroxyl group and no radical polymerizable group or acid group, and alkyl(meth)acrylate structural units having no hydroxyl group, no radical polymerizable group or acid group. Examples of monomers that form alkyl(meth)acrylate structural units that have a hydroxyl group and neither a radically polymerizable group nor an acid group include hydroxyethyl(meth)acrylate and 4-hydroxyethyl(meth)acrylate. Examples of monomers that form alkyl(meth)acrylate structural units that have no hydroxyl group, radically polymerizable group, or acid group include alkyl(meth)acrylates that have a monocyclic or polycyclic aliphatic hydrocarbon group (e.g., dicyclopentanyl(meth)acrylate, cyclohexyl(meth)acrylate, isobornyl(meth)acrylate, 1-adamantyl(meth)acrylate, etc.) and alkyl(meth)acrylates that have a linear or branched aliphatic hydrocarbon group (e.g., methyl(meth)acrylate, butyl(meth)acrylate, etc.).
[0097] The content of alkyl (meth)acrylate structural units having a hydroxyl group and neither a radically polymerizable group nor an acid group is preferably 0 to 5 mass %, more preferably 1 to 3 mass %, based on the total amount of all structural units contained in the alkali-soluble resin. The content of alkyl (meth)acrylate structural units having no hydroxyl group, radically polymerizable group, or acid group is preferably 0 to 5 mass %, more preferably 1 to 3 mass %, based on the total amount of all structural units contained in the alkali-soluble resin.
[0098] The alkali-soluble resin may contain one kind of other structural unit alone, or may contain two or more kinds of other structural units.
[0099] The weight average molecular weight (Mw) of the alkali-soluble resin is preferably 5,000 or more, more preferably from 5,000 to 100,000, and even more preferably from 7,000 to 50,000.
[0100] The dispersity (weight average molecular weight Mw / number average molecular weight Mn) of the alkali-soluble resin is preferably from 1.0 to 3.0, more preferably from 1 to 2.5, from the viewpoint of film strength.
[0101] The acid value of the alkali-soluble resin is preferably 50 mgKOH / g or more, more preferably 60 mgKOH / g or more, further preferably 70 mgKOH / g or more, and particularly preferably 80 mgKOH / g or more, from the viewpoint of developability. The upper limit of the acid value of the alkali-soluble resin is preferably 200 mgKOH / g or less, and more preferably 150 mgKOH / g or less, in order to prevent dissolution in a developer. As the acid value, a theoretical acid value calculated by the calculation method described in, for example, paragraph
[0063] of JP-A-2004-149806 or paragraph
[0070] of JP-A-2012-211228 can be used.
[0102] The photosensitive composition layer may contain one kind of alkali-soluble resin alone, or may contain two or more kinds of alkali-soluble resins.
[0103] The photosensitive composition layer may contain residual monomers of each of the structural units of the alkali-soluble resin described above. From the viewpoints of patterning property and reliability, the content of the residual monomer is preferably 5,000 ppm by mass or less, more preferably 2,000 ppm by mass or less, and even more preferably 500 ppm by mass or less, based on the total mass of the alkali-soluble resin. Although there is no particular lower limit, it is preferably 1 ppm by mass or more, and more preferably 10 ppm by mass or more. From the viewpoints of patterning property and reliability, the residual monomer of each structural unit of the alkali-soluble resin is preferably 3,000 mass ppm or less, more preferably 600 mass ppm or less, and even more preferably 100 mass ppm or less, based on the total mass of the photosensitive composition layer. Although there is no particular lower limit, it is preferably 0.1 mass ppm or more, and more preferably 1 mass ppm or more.
[0104] The amount of residual monomers in the synthesis of an alkali-soluble resin by a polymer reaction is also preferably within the above range. For example, when the alkali-soluble resin is synthesized by reacting glycidyl acrylate with a carboxylic acid side chain, the content of glycidyl acrylate is preferably within the above range. The amount of the residual monomer can be measured by a known method such as liquid chromatography or gas chromatography.
[0105] The content of the alkali-soluble resin is preferably from 10 to 90% by mass, more preferably from 20 to 80% by mass, and even more preferably from 25 to 70% by mass, based on the total mass of the photosensitive composition layer, from the viewpoint of developability.
[0106] [First blocked isocyanate compound] The photosensitive composition layer includes a first blocked isocyanate compound. A blocked isocyanate compound refers to a compound having a structure in which the isocyanate group of an isocyanate is protected (so-called masked) with a blocking agent. In this specification, the term "blocked isocyanate compound" includes not only the "first blocked isocyanate compound" but also the "second blocked isocyanate compound" described below. Furthermore, a structure in which an isocyanate group is protected with a blocking agent may be referred to as a "blocked isocyanate group."
[0107] The NCO value of the first blocked isocyanate compound is 4.5 mmol / g or more, and from the viewpoint of obtaining better effects of the present invention, it is preferably 5.0 mmol / g or more, and more preferably 5.3 mmol / g or more. The upper limit of the NCO value of the first blocked isocyanate compound is preferably 8.0 mmol / g or less, more preferably 6.0 mmol / g or less, even more preferably less than 5.8 mmol / g, and particularly preferably 5.7 mmol / g or less, in terms of obtaining better effects of the present invention. 。
[0108] The dissociation temperature of the first blocked isocyanate compound is preferably from 100 to 160°C, and more preferably from 110 to 150°C.
[0109] In this specification, the term "dissociation temperature of a blocked isocyanate compound" refers to the temperature of an endothermic peak accompanying the deprotection reaction of a blocked isocyanate compound, as measured by DSC (Differential Scanning Calorimetry) analysis using a differential scanning calorimeter. As the differential scanning calorimeter, for example, a differential scanning calorimeter (model: DSC6200) manufactured by Seiko Instruments Inc. can be suitably used. However, the differential scanning calorimeter is not limited to the above-mentioned differential scanning calorimeter.
[0110] Examples of blocking agents having a dissociation temperature of 100 to 160° C. include active methylene compounds (malonic acid diesters (dimethyl malonate, diethyl malonate, di-n-butyl malonate, di-2-ethylhexyl malonate, etc.)) and oxime compounds (formaldoxime, acetaldoxime, acetoxime, methyl ethyl ketoxime, cyclohexanone oxime, and other compounds having a structure represented by -C(=N-OH)- in the molecule). Among the above, oxime compounds are preferred as blocking agents having a dissociation temperature of 100 to 160° C. in terms of storage stability.
[0111] The first blocked isocyanate compound preferably has a ring structure in order to obtain better effects of the present invention. Examples of the ring structure include an aliphatic hydrocarbon ring, an aromatic hydrocarbon ring, and a heterocycle, and in order to obtain better effects of the present invention, an aliphatic hydrocarbon ring and an aromatic hydrocarbon ring are preferred, and an aliphatic hydrocarbon ring is more preferred. Specific examples of the aliphatic hydrocarbon ring include a cyclopentane ring and a cyclohexane ring, and among these, a cyclohexane ring is preferable. Specific examples of the aromatic hydrocarbon ring include a benzene ring and a naphthalene ring, with the benzene ring being preferred. A specific example of the heterocyclic ring is an isocyanurate ring. When the first blocked isocyanate compound has a ring structure, from the viewpoint of better effects of the present invention, the number of rings is preferably 1 to 2, and more preferably 1. When the first blocked isocyanate compound contains a condensed ring, the number of rings constituting the condensed ring is counted, and for example, the number of rings in a naphthalene ring is counted as 2.
[0112] The number of blocked isocyanate groups in the first blocked isocyanate compound is preferably 2 to 5, more preferably 2 to 3, and even more preferably 2, in terms of excellent strength of the formed pattern and excellent effects of the present invention.
[0113] The first blocked isocyanate compound is preferably a blocked isocyanate compound represented by formula Q, since the effects of the present invention are more excellent. B 1 -A 1 -L 1 -A 2 -B 2 formula Q
[0114] In formula Q, B 1 and B. 2 each independently represents a blocked isocyanate group. The blocked isocyanate group is not particularly limited, but from the viewpoint of obtaining a more excellent effect of the present invention, a group in which an isocyanate group is blocked with an oxime compound is preferred, and a group in which an isocyanate group is blocked with methyl ethyl ketoxime (specifically, a group represented by *-NH-C(=O)-ON=C(CH3)-C2H5, where * is A 1 Or A 2 represents the bonding position with.) is more preferred. B 1 and B. 2 are preferably the same group.
[0115] In formula Q, A 1 and A 2 each independently represents a single bond or an alkylene group having 1 to 10 carbon atoms, and preferably an alkylene group having 1 to 10 carbon atoms. The alkylene group may be linear, branched or cyclic, but is preferably linear. The alkylene group has 1 to 10 carbon atoms, preferably 1 to 5 carbon atoms, more preferably 1 to 3 carbon atoms, and even more preferably 1 carbon atom, in terms of better effects of the present invention. A 1 and A 2 are preferably the same group.
[0116] In formula Q, L 1 represents a divalent linking group. Specific examples of the divalent linking group include divalent hydrocarbon groups. Specific examples of the divalent hydrocarbon group include a divalent saturated hydrocarbon group, a divalent aromatic hydrocarbon group, and a group formed by linking two or more of these groups. The divalent saturated hydrocarbon group may be linear, branched or cyclic, and is preferably cyclic in view of better effects of the present invention. The number of carbon atoms in the divalent saturated hydrocarbon group is preferably 4 to 15, more preferably 5 to 10, and even more preferably 5 to 8, in view of better effects of the present invention. The divalent aromatic hydrocarbon group preferably has 5 to 20 carbon atoms, and an example of the group is a phenylene group. The divalent aromatic hydrocarbon group may have a substituent (for example, an alkyl group). Among these, the divalent linking group is preferably a linear, branched or cyclic divalent saturated hydrocarbon group having 5 to 10 carbon atoms, a group in which a cyclic saturated hydrocarbon group having 5 to 10 carbon atoms is linked to a linear alkylene group having 1 to 3 carbon atoms, a divalent aromatic hydrocarbon group which may have a substituent, or a group in which a divalent aromatic hydrocarbon group is linked to a linear alkylene group having 1 to 3 carbon atoms, more preferably a cyclic divalent saturated hydrocarbon group having 5 to 10 carbon atoms or a phenylene group which may have a substituent, still more preferably a cyclohexylene group or a phenylene group which may have a substituent, and particularly preferably a cyclohexylene group.
[0117] The blocked isocyanate compound represented by formula Q is particularly preferably a blocked isocyanate compound represented by formula QA, since the effects of the present invention are more excellent. B 1a -A 1a -L 1a -A 2a -B 2a QA
[0118] In the QA section, B 1a and B. 2a Each independently represents a blocked isocyanate group. 1a and B. 2a A preferred embodiment of the formula Q is 1 and B. 2 is the same as:
[0119] In the QA, A 1a and A 2a Each of A independently represents a divalent linking group. 1a and A 2a A preferred embodiment of the divalent linking group in formula Q is 1 and A 2 is the same as:
[0120] In the formula QA, L 1a represents a cyclic divalent saturated hydrocarbon group or a divalent aromatic hydrocarbon group. L 1a The cyclic divalent saturated hydrocarbon group in preferably has 5 to 10 carbon atoms, more preferably 5 to 8 carbon atoms, further preferably 5 or 6 carbon atoms, and particularly preferably 6 carbon atoms. L 1a A preferred embodiment of the divalent aromatic hydrocarbon group in the formula Q is 1 is the same as: Among them, L 1a is preferably a cyclic divalent saturated hydrocarbon group, more preferably a cyclic divalent saturated hydrocarbon group having 5 to 10 carbon atoms, still more preferably a cyclic divalent saturated hydrocarbon group having 5 to 10 carbon atoms, particularly preferably a cyclic divalent saturated hydrocarbon group having 5 to 6 carbon atoms, and most preferably a cyclohexylene group. L 1a When is a cyclohexylene group, the blocked isocyanate compound represented by the formula QA may be an isomer mixture of cis and trans isomers (hereinafter also referred to as a "cis-trans isomer mixture"). The mass ratio of cis isomer to trans isomer is preferably cis / trans=10 / 90 to 90 / 10, and more preferably cis / trans=40 / 60 to 60 / 40.
[0121] Specific examples of the first blocked isocyanate compound are shown below, but the first blocked isocyanate compound is not limited thereto.
[0122] [ka]
[0123] The photosensitive composition layer may contain one kind of first blocked isocyanate compound alone, or may contain two or more kinds of first blocked isocyanate compounds.
[0124] The content of the first blocked isocyanate compound is preferably 1 to 20 mass %, more preferably 2 to 15 mass %, and even more preferably 2.5 to 13 mass %, relative to the total mass of the photosensitive composition layer, in order to obtain better effects of the present invention.
[0125] The first blocked isocyanate compound is, for example, a compound having an isocyanate group (for example, B 1 and B. 2 is an isocyanate group) with the above blocking agent.
[0126] [Second blocked isocyanate compound] The photosensitive composition layer preferably further contains a blocked isocyanate compound having an NCO value of less than 4.5 mmol / g (hereinafter also referred to as a "second blocked isocyanate compound"), which can suppress the generation of development residues after the photosensitive composition layer is subjected to pattern exposure and development.
[0127] The NCO value of the second blocked isocyanate compound is less than 4.5 mmol / g, preferably from 3.0 to 4.5 mmol / g, more preferably from 3.3 to 4.4 mmol / g, and even more preferably from 3.5 to 4.3 mmol / g.
[0128] The dissociation temperature of the second blocked isocyanate compound is preferably from 100 to 160°C, and more preferably from 110 to 150°C. Specific examples of the blocking agent having a dissociation temperature of 100 to 160° C. are as described above.
[0129] The second blocked isocyanate compound preferably has an isocyanurate structure from the viewpoint of improving the brittleness of the film or improving the adhesion to the transfer target, etc. A blocked isocyanurate compound having an isocyanurate structure can be obtained, for example, by protecting hexamethylene diisocyanate through isocyanuration.
[0130] As the blocked isocyanurate compound having an isocyanurate structure, a compound having an oxime structure in which an oxime compound is used as a blocking agent is preferred, since it is easier to set the dissociation temperature in a preferred range and to reduce development residues than a compound not having an oxime structure.
[0131] The second blocked isocyanate compound may have a polymerizable group from the viewpoint of the strength of the pattern to be formed. The polymerizable group is preferably a radically polymerizable group. Examples of the polymerizable group include ethylenically unsaturated groups such as (meth)acryloxy groups, (meth)acrylamide groups, and styryl groups, as well as groups having an epoxy group such as glycidyl groups. Among the above, the polymerizable group is preferably an ethylenically unsaturated group, and more preferably a (meth)acryloxy group, from the viewpoints of the surface condition of the resulting pattern, development speed, and reactivity.
[0132] Specific examples of the second blocked isocyanate compound are shown below, but the second blocked isocyanate compound is not limited thereto.
[0133] [ka]
[0134] The second blocked isocyanate compound may be a commercially available product. Examples of commercially available blocked isocyanate compounds include Karenz (registered trademark) AOI-BM, Karenz (registered trademark) MOI-BM, Karenz (registered trademark) AOI-BP, Karenz (registered trademark) MOI-BP, etc. (all manufactured by Showa Denko K.K.), and the blocked Duranate series (e.g., Duranate (registered trademark) TPA-B80E, manufactured by Asahi Kasei Chemicals Corporation).
[0135] The photosensitive composition layer may contain one type of second blocked isocyanate compound alone, or may contain two or more types of second blocked isocyanate compounds.
[0136] When the photosensitive composition layer contains the second blocked isocyanate compound, the content of the second blocked isocyanate compound is preferably 5 to 20 mass %, more preferably 7 to 17 mass %, and even more preferably 10 to 15 mass %, relative to the total mass of the photosensitive composition layer, from the viewpoint of further reducing the generation of development residues.
[0137] When the photosensitive composition layer contains the second blocked isocyanate compound, the mass ratio of the content of the first blocked isocyanate compound to the content of the second blocked isocyanate compound (first blocked isocyanate compound / second blocked isocyanate compound) is preferably 0.1 to 1.5, more preferably 0.2 to 1.0, and even more preferably 0.2 to 0.8, from the viewpoint of bending resistance.
[0138] [Polymer containing a structural unit having a carboxylic acid anhydride structure] The photosensitive composition layer may further contain a polymer containing a structural unit having a carboxylic acid anhydride structure (hereinafter, also referred to as "polymer B") as a binder. When the photosensitive composition layer contains polymer B, the developability and strength after curing can be improved.
[0139] The carboxylic acid anhydride structure may be either a chain carboxylic acid anhydride structure or a cyclic carboxylic acid anhydride structure, with a cyclic carboxylic acid anhydride structure being preferred. The ring of the cyclic carboxylic acid anhydride structure is preferably a 5- to 7-membered ring, more preferably a 5- or 6-membered ring, and even more preferably a 5-membered ring.
[0140] The structural unit having a carboxylic acid anhydride structure is preferably a structural unit containing a divalent group obtained by removing two hydrogen atoms from a compound represented by the following formula P-1 in the main chain, or a structural unit in which a monovalent group obtained by removing one hydrogen atom from a compound represented by the following formula P-1 is bonded to the main chain directly or via a divalent linking group.
[0141] [ka]
[0142] In formula P-1, R A1a represents a substituent, n 1a R A1a may be the same or different, Z 1a represents a divalent group forming a ring containing -C(=O)-OC(=O)-, n 1a represents an integer greater than or equal to 0.
[0143] R A1a Examples of the substituent represented by the formula (I) include an alkyl group.
[0144] Z 1a As the alkylene group, an alkylene group having 2 to 4 carbon atoms is preferable, an alkylene group having 2 or 3 carbon atoms is more preferable, and an alkylene group having 2 carbon atoms is even more preferable.
[0145] n 1a represents an integer equal to or greater than 0. 1a When represents an alkylene group having 2 to 4 carbon atoms, n 1a is preferably an integer of 0 to 4, more preferably an integer of 0 to 2, and even more preferably 0.
[0146] n 1a If represents an integer of 2 or more, there are multiple R A1amay be the same or different. In addition, if there are multiple R A1a may be bonded to each other to form a ring, but preferably do not bond to each other to form a ring.
[0147] As the structural unit having a carboxylic acid anhydride structure, a structural unit derived from an unsaturated carboxylic acid anhydride is preferable, a structural unit derived from an unsaturated cyclic carboxylic acid anhydride is more preferable, a structural unit derived from an unsaturated aliphatic cyclic carboxylic acid anhydride is even more preferable, a structural unit derived from maleic anhydride or itaconic anhydride is particularly preferable, and a structural unit derived from maleic anhydride is most preferable.
[0148] The structural unit having a carboxylic acid anhydride structure in the polymer B may be of one type alone or may be of two or more types.
[0149] The content of the structural unit having a carboxylic acid anhydride structure relative to the total amount of polymer B is preferably from 0 to 60 mol %, more preferably from 5 to 40 mol %, and even more preferably from 10 to 35 mol %. The photosensitive composition layer may contain one kind of polymer B alone, or may contain two or more kinds of polymer B.
[0150] In terms of patterning properties and reliability, the content of the residual monomers of each structural unit of polymer B in the photosensitive composition layer is preferably 1000 ppm by mass or less, more preferably 500 ppm by mass or less, and even more preferably 100 ppm by mass or less, based on the total mass of polymer B. There is no particular lower limit, but it is preferably 0.1 ppm by mass or more, and more preferably 1 ppm by mass or more.
[0151] When the photosensitive composition layer contains polymer B, the content of polymer B is preferably 0.1 to 30 mass %, more preferably 0.2 to 20 mass %, even more preferably 0.5 to 20 mass %, and particularly preferably 1 to 20 mass %, relative to the total mass of the photosensitive composition layer, from the viewpoints of developability and strength after curing.
[0152] [Heterocyclic compounds] The photosensitive composition layer preferably contains a heterocyclic compound. The heterocycle contained in the heterocyclic compound may be either a monocyclic or polycyclic heterocycle. Examples of heteroatoms contained in the heterocyclic compound include a nitrogen atom, an oxygen atom, and a sulfur atom. The heterocyclic compound preferably contains at least one atom selected from the group consisting of a nitrogen atom, an oxygen atom, and a sulfur atom, and more preferably contains a nitrogen atom.
[0153] Examples of heterocyclic compounds include triazole compounds, benzotriazole compounds, tetrazole compounds, thiadiazole compounds, triazine compounds, rhodanine compounds, thiazole compounds, benzothiazole compounds, benzimidazole compounds, benzoxazole compounds, and pyrimidine compounds (e.g., isonicotinamide). Among the above, the heterocyclic compound is preferably at least one compound selected from the group consisting of triazole compounds, benzotriazole compounds, tetrazole compounds, thiadiazole compounds, triazine compounds, rhodanine compounds, thiazole compounds, benzimidazole compounds, and benzoxazole compounds, and more preferably at least one compound selected from the group consisting of triazole compounds, benzotriazole compounds, tetrazole compounds, thiadiazole compounds, thiazole compounds, benzothiazole compounds, benzimidazole compounds, and benzoxazole compounds.
[0154] Preferable specific examples of the heterocyclic compound are shown below. As the triazole compound and the benzotriazole compound, the following compounds can be exemplified.
[0155] [ka]
[0156] [ka]
[0157] Examples of the tetrazole compound include the following compounds.
[0158] [ka]
[0159] [ka]
[0160] Examples of the thiadiazole compound include the following compounds.
[0161] [ka]
[0162] Examples of the triazine compound include the following compounds.
[0163] [ka]
[0164] Examples of rhodanine compounds include the following compounds.
[0165] [ka]
[0166] Examples of the thiazole compound include the following compounds.
[0167] [ka]
[0168] Examples of the benzothiazole compound include the following compounds.
[0169] [ka]
[0170] Examples of the benzimidazole compound include the following compounds.
[0171] [ka]
[0172] [ka]
[0173] Examples of the benzoxazole compound include the following compounds.
[0174] [ka]
[0175] The photosensitive composition layer may contain one kind of heterocyclic compound alone, or may contain two or more kinds of heterocyclic compounds.
[0176] When the photosensitive composition layer contains a heterocyclic compound, the content of the heterocyclic compound is preferably 0.01 to 20 mass %, more preferably 0.1 to 10 mass %, still more preferably 0.3 to 8 mass %, and particularly preferably 0.5 to 5 mass %, relative to the total mass of the photosensitive composition layer.
[0177] [Aliphatic thiol compounds] The photosensitive composition layer preferably contains an aliphatic thiol compound. When the photosensitive composition layer contains an aliphatic thiol compound, the aliphatic thiol compound undergoes an ene-thiol reaction with a radical polymerizable compound having an ethylenically unsaturated group, thereby suppressing the cure shrinkage of the film formed and reducing stress.
[0178] The aliphatic thiol compound is preferably a monofunctional aliphatic thiol compound or a polyfunctional aliphatic thiol compound (that is, a di- or higher functional aliphatic thiol compound).
[0179] Among the above, as the aliphatic thiol compound, for example, from the viewpoint of the adhesion of the pattern to be formed (particularly the adhesion after exposure), a polyfunctional aliphatic thiol compound is preferable.
[0180] In the present disclosure, a "polyfunctional aliphatic thiol compound" refers to an aliphatic compound having two or more thiol groups (also called "mercapto groups") in the molecule.
[0181] The polyfunctional aliphatic thiol compound is preferably a low molecular weight compound having a molecular weight of at least 100. Specifically, the molecular weight of the polyfunctional aliphatic thiol compound is more preferably 100 to 1,500, and further preferably 150 to 1,000.
[0182] The number of functional groups of the polyfunctional aliphatic thiol compound is preferably 2 to 10, more preferably 2 to 8, and even more preferably 2 to 6, from the viewpoint of adhesion of the formed pattern.
[0183] Examples of polyfunctional aliphatic thiol compounds include trimethylolpropane tris(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, pentaerythritol tetrakis(3-mercaptobutyrate), 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylolethane tris(3-mercaptobutyrate), tris[(3-mercaptopropionyloxy)ethyl]isocyanurate, trimethylolpropane tris(3-mercaptopropionyloxy)ethyl]isocyanurate, ester), pentaerythritol tetrakis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate), dipentaerythritol hexakis(3-mercaptopropionate), ethylene glycol bisthiopropionate, 1,4-bis(3-mercaptobutyryloxy)butane, 1,2-ethanedithiol, 1,3-propanedithiol, 1,6-hexamethylenedithiol, 2,2'-(ethylenedithio)diethanethiol, meso-2,3-dimercaptosuccinic acid, and di(mercaptoethyl)ether.
[0184] Among the above, the polyfunctional aliphatic thiol compound is preferably at least one compound selected from the group consisting of trimethylolpropane tris(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, and 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione.
[0185] Examples of monofunctional aliphatic thiol compounds include 1-octanethiol, 1-dodecanethiol, β-mercaptopropionic acid, methyl-3-mercaptopropionate, 2-ethylhexyl-3-mercaptopropionate, n-octyl-3-mercaptopropionate, methoxybutyl-3-mercaptopropionate, and stearyl-3-mercaptopropionate.
[0186] The photosensitive composition layer may contain one kind of aliphatic thiol compound alone, or may contain two or more kinds of aliphatic thiol compounds.
[0187] When the photosensitive composition layer contains an aliphatic thiol compound, the content of the aliphatic thiol compound is preferably 5 mass% or more, more preferably 5 to 50 mass%, even more preferably 5 to 30 mass%, and particularly preferably 8 to 20 mass%, relative to the total mass of the photosensitive composition layer.
[0188] [Surfactants] The photosensitive composition layer preferably contains a surfactant. Examples of the surfactant include those described in paragraph
[0017] of Japanese Patent No. 4502784 and paragraphs
[0060] to
[0071] of JP-A-2009-237362.
[0189] The surfactant is preferably a nonionic surfactant, a fluorine-based surfactant or a silicon-based surfactant.
[0190] Commercially available fluorine-based surfactants include, for example, Megafac F-171, F-172, F-173, F-176, F-177, F-141, F-142, F-143, F-144, F-437, F-475, F-477, F-479, F-482, F-551-A, F-552, F-554, F-555-A, F-556, F-557, F-558, F-559, F-560, F-561, F-565, F -563, F-568, F-575, F-780, EXP, MFS-330, MFS-578, MFS-579, MFS-586, MFS-587, R-41, R-41-LM, R-01, R-40, R-40-LM, RS-43, TF-1956, RS-90, R-94, RS-72-K, DS-21 (all manufactured by DIC Corporation), Fluorad FC430, FC431, FC171 (all manufactured by Sumitomo 3M Limited), Surflon S-382, SC-101, SC-103, SC-104, SC-105, SC-1068, SC-381, SC-383, S-393, KH-40 (all manufactured by AGC Inc.), PolyFox PF636, PF656, PF6320, PF6520, PF7002 (all manufactured by OMNOVA), Futergent Examples of such products include 710FL, 710FM, 610FM, 601AD, 601ADH2, 602A, 215M, 245F, 251, 212M, 250, 209F, 222F, 208G, 710LA, 710FS, 730LM, 650AC, 681, and 683 (all manufactured by NEOS Corporation). Also suitable for use as the fluorosurfactant are acrylic compounds that have a molecular structure with a functional group containing a fluorine atom, and when heat is applied, the functional group containing the fluorine atom is broken and the fluorine atom volatilizes. Examples of such fluorosurfactants include the Megafac DS series manufactured by DIC Corporation (The Chemical Daily (February 22, 2016), Nikkei Business Daily (February 23, 2016)), such as Megafac DS-21. As the fluorine-based surfactant, it is also preferable to use a polymer of a fluorine atom-containing vinyl ether compound having a fluorinated alkyl group or a fluorinated alkylene ether group and a hydrophilic vinyl ether compound. Furthermore, as the fluorosurfactant, a block polymer can also be used. In addition, as the fluorine-based surfactant, a fluorine-containing polymer compound containing a structural unit derived from a (meth)acrylate compound having a fluorine atom and a structural unit derived from a (meth)acrylate compound having two or more (preferably five or more) alkyleneoxy groups (preferably ethyleneoxy groups, propyleneoxy groups) can also be preferably used. As the fluorine-based surfactant, a fluorine-containing polymer having an ethylenically unsaturated bond-containing group in the side chain can also be used, such as Megafac RS-101, RS-102, RS-718K, and RS-72-K (all manufactured by DIC Corporation).
[0191] From the viewpoint of improving environmental compatibility, it is preferable that the fluorosurfactant be a surfactant derived from an alternative material to compounds having a linear perfluoroalkyl group having 7 or more carbon atoms, such as perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS).
[0192] Examples of nonionic surfactants include glycerol, trimethylolpropane, trimethylolethane, and their ethoxylates and propoxylates (e.g., glycerol propoxylate, glycerol ethoxylate, etc.), polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene nonylphenyl ether, polyethylene glycol dilaurate, polyethylene glycol distearate, sorbitan fatty acid esters, Pluronic L10, L31, L61, L62, 10R5, 17R2, 25R2 (all manufactured by BASF), Tetronic 304, 701, 704, 901, 904, 150R1 (all manufactured by BASF), and Solsperse. 20000 (all manufactured by Lubrizol Nippon Co., Ltd.), NCW-101, NCW-1001, NCW-1002 (all manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), Paionin D-6112, D-6112-W, D-6315 (all manufactured by Takemoto Oil Co., Ltd.), Olfine E1010, Surfynol 104, 400, 440 (all manufactured by Nissin Chemical Industry Co., Ltd.), and the like.
[0193] Commercially available silicon-based surfactants include DOWSIL 8032 ADDITIVE, Toray Silicone DC3PA, Toray Silicone SH7PA, Toray Silicone DC11PA, Toray Silicone SH21PA, Toray Silicone SH28PA, Toray Silicone SH29PA, Toray Silicone SH30PA, and Toray Silicone SH8400 (all manufactured by Toray Dow Corning Co., Ltd.), as well as X-22-4952, X-22-4272, X-22-6266, KF-351A, K354L, KF-355A, and KF- 945, KF-640, KF-642, KF-643, X-22-6191, X-22-4515, KF-6004, KP-341, KF-6001, KF-6002 (all manufactured by Shin-Etsu Silicones Co., Ltd.), F-4440, TSF-4300, TSF-4445, TSF-4460, TSF-4452 (all manufactured by Momentive Performance Materials), BYK307, BYK323, BYK330 (all manufactured by BYK-Chemie).
[0194] The photosensitive composition layer may contain one type of surfactant alone, or may contain two or more types of surfactants.
[0195] When the photosensitive composition layer contains a surfactant, the content of the surfactant is preferably from 0.01 to 3 mass %, more preferably from 0.05 to 1 mass %, and even more preferably from 0.1 to 0.8 mass %, based on the total mass of the photosensitive composition layer.
[0196] [Hydrogen donor compounds] The photosensitive composition layer preferably contains a hydrogen donor compound. The hydrogen donor compound has the effect of further improving the sensitivity of the photopolymerization initiator to actinic rays and suppressing the polymerization inhibition of the polymerizable compound caused by oxygen.
[0197] Examples of the hydrogen donor compound include amines such as those described in MR Sander et al., Journal of Polymer Society, Vol. 10, p. 3173 (1972), JP-B-020189 / 1969, JP-A-51-082102, JP-A-52-134692, JP-A-59-138205, JP-A-60-084305, JP-A-62-018537, JP-A-64-033104, and Research Disclosure No. 33825.
[0198] Examples of hydrogen donor compounds include triethanolamine, p-dimethylaminobenzoic acid ethyl ester, p-formyldimethylaniline, and p-methylthiodimethylaniline.
[0199] Further, examples of hydrogen donor compounds include amino acid compounds (e.g., N-phenylglycine), organometallic compounds (e.g., tributyltin acetate) described in JP-B-48-042965, hydrogen donors described in JP-B-55-034414, and sulfur compounds (e.g., trithiane) described in JP-A-6-308727.
[0200] The photosensitive composition layer may contain one kind of hydrogen donor compound alone, or may contain two or more kinds of hydrogen donor compounds.
[0201] When the photosensitive composition layer contains a hydrogen donor compound, the content of the hydrogen donor compound is preferably 0.01 to 10 mass %, more preferably 0.03 to 5 mass %, and even more preferably 0.05 to 3 mass %, relative to the total mass of the photosensitive composition layer, from the viewpoint of improving the curing rate through a balance between the polymerization growth rate and chain transfer.
[0202] [Other ingredients] The photosensitive composition layer may contain components other than those described above (hereinafter, also referred to as "other components"). Examples of the other components include particles (e.g., metal oxide particles) and colorants. Further, examples of other components include the thermal polymerization inhibitor described in paragraph
[0018] of Japanese Patent No. 4,502,784, and other additives described in paragraphs
[0058] to
[0071] of JP-A-2000-310706.
[0203] The photosensitive composition layer may contain particles for the purpose of adjusting the refractive index, light transmittance, etc. Examples of the particles include metal oxide particles. The metals in the metal oxide particles include metalloids such as B, Si, Ge, As, Sb, and Te.
[0204] The average primary particle diameter of the particles is preferably 1 to 200 nm, more preferably 3 to 80 nm, from the viewpoint of pattern transparency. The average primary particle diameter of the particles is calculated by measuring the particle diameters of 200 random particles using an electron microscope and arithmetically averaging the measurement results. When the shape of the particles is not spherical, the longest side is taken as the particle diameter.
[0205] The photosensitive composition layer may contain one type of particle or two or more types of particles. When the photosensitive composition layer contains particles, it may contain one type of particle or two or more types of particles having different metal species, sizes, etc.
[0206] The photosensitive composition layer preferably does not contain particles or the particle content is more than 0 mass% and not more than 35 mass% relative to the total mass of the photosensitive composition layer, more preferably does not contain particles or the particle content is more than 0 mass% and not more than 10 mass% relative to the total mass of the photosensitive composition layer, even more preferably does not contain particles or the particle content is more than 0 mass% and not more than 5 mass% relative to the total mass of the photosensitive composition layer, particularly preferably does not contain particles or the particle content is more than 0 mass% and not more than 1 mass% relative to the total mass of the photosensitive composition layer, and most preferably does not contain particles.
[0207] The photosensitive composition layer may contain a small amount of a colorant (for example, a pigment or a dye). However, from the standpoint of transparency, for example, it is preferable that the photosensitive composition layer contains substantially no colorant. When the photosensitive composition layer contains a colorant, the content of the colorant is preferably less than 1 mass %, more preferably less than 0.1 mass %, based on the total mass of the photosensitive composition layer.
[0208] [Impurities etc.] The photosensitive composition layer may contain a certain amount of impurities. Specific examples of impurities include sodium, potassium, magnesium, calcium, iron, manganese, copper, aluminum, titanium, chromium, cobalt, nickel, zinc, tin, halogens, and ions thereof. Among them, halide ions, sodium ions, and potassium ions are easily mixed in as impurities, so it is preferable to set the contents to the following amounts.
[0209] The content of impurities in the photosensitive composition layer is preferably 80 ppm or less, more preferably 10 ppm or less, and even more preferably 2 ppm or less, by mass. The content of impurities in the photosensitive composition layer can be 1 ppb or more, and can be 0.1 ppm or more, by mass.
[0210] Methods for keeping the amount of impurities within the above range include selecting raw materials for the photosensitive composition layer that contain a small amount of impurities, preventing impurities from being mixed in during the formation of the photosensitive composition layer, and removing the impurities by washing. By such methods, the amount of impurities can be kept within the above range.
[0211] The amount of impurities can be quantified by known methods such as ICP (Inductively Coupled Plasma) emission spectrometry, atomic absorption spectrometry, and ion chromatography.
[0212] The content of compounds such as benzene, formaldehyde, trichloroethylene, 1,3-butadiene, carbon tetrachloride, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, and hexane in the photosensitive composition layer is preferably low. The content of these compounds in the photosensitive composition layer is preferably 100 ppm or less, more preferably 20 ppm or less, and even more preferably 4 ppm or less, by mass. The lower limit can be 10 ppb or more, and can be 100 ppb or more, by mass. The content of these compounds can be suppressed in the same manner as the above-mentioned metal impurities. They can also be quantified by known measurement methods.
[0213] The water content in the photosensitive composition layer is preferably from 0.01 to 1.0% by mass, and more preferably from 0.05 to 0.5% by mass, from the viewpoint of improving reliability and lamination properties.
[0214] [Thickness of photosensitive composition layer] The upper limit of the thickness of the photosensitive composition layer is preferably 20.0 μm or less, more preferably 15.0 μm or less, and even more preferably 12.0 μm or less, from the viewpoint of coatability. The lower limit of the thickness of the photosensitive composition is preferably 0.05 μm or more, and from the viewpoint of obtaining superior effects of the present invention, is more preferably 3.0 μm or more, further preferably 4.0 μm or more, and particularly preferably 5.0 μm or more. The thickness of the photosensitive composition layer is calculated as the average value of measurements at any five points by cross-sectional observation using a scanning electron microscope (SEM).
[0215] [Refractive Index of Photosensitive Composition Layer] The refractive index of the photosensitive composition layer is preferably from 1.47 to 1.56, and more preferably from 1.49 to 1.54.
[0216] [Color of photosensitive composition layer] The photosensitive composition layer is preferably achromatic. * The value is preferably −1.0 to 1.0, and the b * The value is preferably in the range of -1.0 to 1.0. The hue of the photosensitive composition layer can be measured using a color difference meter (CR-221, manufactured by Minolta Co., Ltd.).
[0217] [NCO value of photosensitive composition layer] The NCO value of the photosensitive composition layer is preferably greater than 0.50 mmol / g, more preferably 0.55 mmol / g or more, and even more preferably 0.60 mmol / g or more, in terms of achieving better effects of the present invention. The upper limit of the NCO value of the photosensitive composition layer is preferably 1.0 mmol / g or less, more preferably less than 0.80 mmol / g, and even more preferably 0.70 mmol / g or less, in terms of obtaining better effects of the present invention. 。
[0218] [Transmittance of Photosensitive Composition Layer] The visible light transmittance per 1.0 μm of the film thickness of the photosensitive composition layer is preferably 80% or more, more preferably 90% or more, and most preferably 95% or more. As for the visible light transmittance, it is preferable that all of the average transmittance at wavelengths of 400 nm to 800 nm, the minimum transmittance at wavelengths of 400 nm to 800 nm, and the transmittance at a wavelength of 400 nm satisfy the above. Preferred values of the transmittance include, for example, 87%, 92%, and 98%. The same applies to the transmittance per 1.0 μm of film thickness of the cured film of the photosensitive composition layer.
[0219] [Moisture permeability of photosensitive composition layer] The moisture permeability of the pattern (cured film of the photosensitive composition layer) obtained by curing the photosensitive composition layer at a film thickness of 40 μm is 500 g / m from the viewpoint of rust prevention of the electrodes or wiring and device reliability. 2 / 24hr or less is preferable, and 300g / m 2 / 24hr or less is more preferable, and 100g / m 2 It is more preferable that the time is 24 hours or less. The moisture permeability was measured by exposing the photosensitive composition layer to i-rays at a dose of 300 mJ / cm 2 After exposure to light at 40° C., the photosensitive composition layer is post-baked at 145° C. for 30 minutes to cure the photosensitive composition layer, and the cured film is used for the measurement. The moisture permeability is measured in accordance with the cup method of JIS Z 0208. It is preferable that the moisture permeability is within the above range under any of the test conditions of temperature 40° C. / humidity 90%, temperature 65° C. / humidity 90%, and temperature 80° C. / humidity 95%. A specific preferred value is, for example, 80 g / m 2 / 24hr, 150g / m 2 / 24hr, 220g / m 2 / 24hr, etc.
[0220] [Dissolution rate of photosensitive composition layer] The dissolution rate of the photosensitive composition layer in a 1.0 mass % aqueous sodium carbonate solution is preferably 0.01 μm / sec or more, more preferably 0.10 μm / sec or more, and even more preferably 0.20 μm / sec or more, from the viewpoint of suppressing residues during development. From the viewpoint of the edge shape of the pattern, the speed is preferably 5.0 μm / sec or less, more preferably 4.0 μm / sec or less, and even more preferably 3.0 μm / sec or less. Specific preferred values include, for example, 1.8 μm / sec, 1.0 μm / sec, and 0.7 μm / sec. The dissolution rate per unit time of the photosensitive composition layer in a 1.0% by mass aqueous sodium carbonate solution is measured as follows. The photosensitive composition layer (thickness in the range of 1.0 to 10 μm) formed on the glass substrate and from which the solvent has been sufficiently removed is subjected to shower development at 25° C. using a 1.0 mass % aqueous sodium carbonate solution until the photosensitive composition layer is completely dissolved (however, the maximum time is 2 minutes). The thickness of the photosensitive composition layer is calculated by dividing the thickness by the time required for the photosensitive composition layer to completely dissolve. If the photosensitive composition layer does not completely dissolve within 2 minutes, the thickness is calculated in the same manner from the amount of change in thickness up to that point.
[0221] The dissolution rate of the cured film of the photosensitive composition layer (within the range of film thickness 1.0 to 10 μm) in a 1.0 mass % aqueous solution of sodium carbonate is preferably 3.0 μm / sec or less, more preferably 2.0 μm / sec or less, further preferably 1.0 μm / sec or less, and most preferably 0.2 μm / sec or less. The cured film of the photosensitive composition layer is formed by exposing the photosensitive composition layer to i-rays at an exposure dose of 300 mJ / cm. 2 This film is obtained by exposure to light at . Specific preferred values include, for example, 0.8 μm / sec, 0.2 μm / sec, and 0.001 μm / sec. For development, a 1 / 4MIN JJX030PP shower nozzle manufactured by Ikeuchi Co., Ltd. is used, and the shower spray pressure is 0.08MPa. Under the above conditions, the shower flow rate per unit time is 1,800mL / min.
[0222] [Swelling ratio of photosensitive composition layer] The swelling ratio of the photosensitive composition layer after exposure to a 1.0 mass % aqueous sodium carbonate solution is preferably 100% or less, more preferably 50% or less, and even more preferably 30% or less, from the viewpoint of improving pattern formability. Swelling ratio of photosensitive resin layer after exposure The swelling ratio with respect to a 1.0% by mass aqueous sodium carbonate solution is measured as follows. A photosensitive resin layer (within the range of film thickness 1.0 to 10 μm) formed on a glass substrate from which the solvent had been sufficiently removed was exposed to 500 mJ / cm 2 of ultra-high pressure mercury lamp. 2The film is exposed to light (i-line measurement). The glass substrate is immersed in a 1.0% by mass aqueous solution of sodium carbonate at 25°C, and the film thickness is measured after 30 seconds. The rate at which the film thickness after immersion has increased relative to the film thickness before immersion is then calculated. Specific preferred values include, for example, 4%, 13%, and 25%.
[0223] [Foreign matter in the photosensitive composition layer] From the viewpoint of pattern forming, the number of foreign matters having a diameter of 1.0 μm or more in the photosensitive composition layer is set to 10 / mm 2 It is preferable that the number of pieces is less than 5 / mm 2 It is more preferable that: The number of foreign objects is measured as follows. From the normal direction to the surface of the photosensitive composition layer, any five regions (1 mm x 1 mm) on the surface of the photosensitive composition layer are visually observed using an optical microscope, and the number of foreign particles having a diameter of 1.0 μm or more in each region is counted, and the arithmetic average is calculated as the number of foreign particles. A specific preferred value is, for example, 0 pieces / mm 2 , 1 piece / mm 2 , 4 pieces / mm 2 , 8 pieces / mm 2 The following can be mentioned:
[0224] [Haze of Dissolved Material in Photosensitive Composition Layer] From the viewpoint of preventing the generation of aggregates during development, 1.0 cm of 1.0 mass % sodium carbonate in 1.0 liter of 30°C aqueous solution was used. 3 The haze of the solution obtained by dissolving the photosensitive resin layer is preferably 60% or less, more preferably 30% or less, further preferably 10% or less, and most preferably 1% or less. Haze shall be measured as follows. First, a 1.0% by mass aqueous solution of sodium carbonate is prepared, and the liquid temperature is adjusted to 30°C. 1.0 cm 3The photosensitive resin layer is placed in the solution. The solution is stirred at 30°C for 4 hours, taking care not to introduce air bubbles. After stirring, the haze of the solution in which the photosensitive resin layer has been dissolved is measured. The haze is measured using a haze meter (product name "NDH4000", manufactured by Nippon Denshoku Industries Co., Ltd.) with a liquid measurement unit and a dedicated liquid measurement cell with an optical path length of 20 mm. Specific preferred values include, for example, 0.4%, 1.0%, 9%, and 24%.
[0225] <Refractive index adjustment layer> The first transfer film may have a refractive index adjustment layer. The position of the refractive index adjustment layer is not particularly limited, but it is preferably arranged in contact with the photosensitive composition layer. In particular, it is preferable that the first transfer film has a temporary support, a photosensitive composition layer, and a refractive index adjustment layer in this order. When the first transfer film further has a protective film described below, it preferably has a temporary support, a photosensitive composition layer, a refractive index adjusting layer, and a protective film in this order.
[0226] The refractive index adjusting layer may be a known refractive index adjusting layer. Examples of materials contained in the refractive index adjusting layer include a binder and particles.
[0227] The binder may be, for example, the alkali-soluble resin described above in the section "Photosensitive composition layer."
[0228] Examples of the particles include zirconium oxide particles (ZrO2 particles), niobium oxide particles (Nb2O5 particles), titanium oxide particles (TiO2 particles), and silicon dioxide particles (SiO2 particles).
[0229] The refractive index matching layer preferably contains a metal oxidation inhibitor, which can suppress oxidation of the metal in contact with the refractive index matching layer. The metal oxidation inhibitor is preferably, for example, a compound having an aromatic ring containing a nitrogen atom in the molecule, and examples of the metal oxidation inhibitor include imidazole, benzimidazole, tetrazole, mercaptothiadiazole, and benzotriazole.
[0230] The refractive index of the refractive index adjusting layer is preferably 1.60 or more, and more preferably 1.63 or more. The upper limit of the refractive index of the refractive index adjusting layer is preferably 2.10 or less, and more preferably 1.85 or less.
[0231] The thickness of the refractive index adjusting layer is preferably 500 nm or less, more preferably 110 nm or less, and even more preferably 100 nm or less. The thickness of the refractive index adjusting layer is preferably 20 nm or more, and more preferably 50 nm or more. The thickness of the refractive index adjusting layer is calculated as the average value of any five points measured by cross-sectional observation using a scanning electron microscope (SEM).
[0232] <Other layers> The first transfer film may include layers other than the above-mentioned temporary support, photosensitive composition layer, and refractive index adjusting layer. Examples of the other layers include a protective film and an antistatic layer.
[0233] The first transfer film may have a protective film for protecting the photosensitive composition layer on the surface opposite to the temporary support. The protective film is preferably a resin film, and a resin film having heat resistance and solvent resistance can be used. Examples of the protective film include polyolefin films such as polypropylene films and polyethylene films. Alternatively, a resin film made of the same material as the above-mentioned temporary support may be used as the protective film.
[0234] The thickness of the protective film is preferably 1 to 100 μm, more preferably 5 to 50 μm, further preferably 5 to 40 μm, and particularly preferably 15 to 30 μm. The thickness of the protective film is preferably 1 μm or more in terms of excellent mechanical strength, and is preferably 100 μm or less in terms of relatively low cost.
[0235] The first transfer film may include an antistatic layer. Because the first transfer film has an antistatic layer, the generation of static electricity when peeling off a film or the like placed on the antistatic layer can be suppressed, and the generation of static electricity due to rubbing with equipment or other films, etc. can also be suppressed, thereby preventing malfunctions in electronic devices, for example. The antistatic layer is preferably disposed between the temporary support and the photosensitive composition layer.
[0236] The antistatic layer is a layer having antistatic properties and contains at least an antistatic agent. The antistatic agent is not particularly limited, and any known antistatic agent can be used.
[0237] [Second embodiment of transfer film] A transfer film in a second embodiment of the present invention (hereinafter also referred to as the "second transfer film") has a temporary support and a photosensitive composition layer arranged on the temporary support, the photosensitive composition layer contains an alkali-soluble resin, a polymerizable compound, a polymerization initiator, and a blocked isocyanate compound, and the NCO value of the photosensitive composition layer is greater than 0.50 mmol / g.
[0238] The second transfer film is characterized in that the NCO value of the photosensitive composition layer is greater than 0.50 mmol / g. Here, an example of a method for forming a protective film using the second transfer film is to contact and bond the second transfer film to a substrate having a conductive layer (sensor electrode and lead wiring), and then to form a patterned protective film through processes such as pattern exposure, development, and post-baking of the photosensitive composition layer of the second transfer film. The alkali-soluble resin contained in the photosensitive composition layer is necessary in terms of the developability of the photosensitive composition layer, but the inventors have discovered that the alkali-soluble resin may cause corrosion of the conductive layer due to the action of acid groups such as carboxyl groups contained in the alkali-soluble resin. To solve this problem, the present inventors have found that the corrosion of the conductive layer can be suppressed by using a photosensitive composition layer having an NCO value of more than 0.50 mmol / g. The reason for this is presumably that the post-bake step generates a sufficient amount of isocyanate groups from the blocked isocyanate compound to react with the acid groups of the alkali-soluble resin, thereby suppressing corrosion of the conductive layer.
[0239] The second transfer film differs from the first transfer film described above in that the NCO value of the photosensitive composition layer must be greater than 0.50 mmol / g, and the NCO value of the blocked isocyanate compound contained in the photosensitive composition layer is not specified.
[0240] The NCO value of the photosensitive composition layer in the second transfer film is greater than 0.50 mmol / g, and is preferably 0.55 mmol / g or more, more preferably 0.60 mmol / g or more, in terms of obtaining better effects of the present invention. The upper limit of the NCO value of the photosensitive composition layer in the second transfer film is preferably 1.0 mmol / g or less, more preferably less than 0.80 mmol / g, and even more preferably 0.70 mmol / g or less, in terms of achieving better effects of the present invention. The method for measuring the NCO value of the photosensitive composition layer is as described above, and therefore the description thereof will be omitted.
[0241] Here, as a method for adjusting the NCO value of the photosensitive composition layer to the above-mentioned range, a method of using the first blocked isocyanate compound described in the section on the first transfer film as the blocked isocyanate compound contained in the photosensitive composition layer can be mentioned. Another method is to adjust the content of the blocked isocyanate compound in the photosensitive composition.
[0242] The components contained or that may be contained in the photosensitive composition layer in the second transfer film are similar to those in the photosensitive composition layer in the first transfer film, and therefore a description thereof will be omitted.
[0243] The physical properties such as thickness, refractive index, and color of the photosensitive composition layer in the second transfer film are also similar to those of the photosensitive composition layer in the first transfer film, and therefore description thereof will be omitted.
[0244] The temporary support of the second transfer film is similar to the temporary support of the first transfer film, and therefore a description thereof will be omitted. The second transfer film may have a refractive index adjusting layer similar to that of the first transfer film, and may also have other layers similar to those of the first transfer film.
[0245] [Method of manufacturing transfer film] The method for producing the transfer film (first transfer film and second transfer film) of the present invention is not particularly limited, and a known method can be used. In the following description, when the term "transfer film" is used simply, it means both the first transfer film and the second transfer film. Among these, a method in which a photosensitive composition is coated on a temporary support, and if necessary, a drying treatment is performed to form a photosensitive composition layer (hereinafter, this method is also referred to as the "coating method") is preferred from the viewpoint of excellent productivity.
[0246] The photosensitive composition used in the coating method preferably contains the components constituting the photosensitive composition layer described above (e.g., a polymerizable compound, an alkali-soluble resin, a polymerization initiator, a blocked isocyanate compound, etc.) and a solvent. The solvent is preferably an organic solvent. Examples of the organic solvent include methyl ethyl ketone, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate (also known as 1-methoxy-2-propyl acetate), diethylene glycol ethyl methyl ether, cyclohexanone, methyl isobutyl ketone, ethyl lactate, methyl lactate, caprolactam, n-propanol, and 2-propanol. The solvent is preferably a mixed solvent of methyl ethyl ketone and propylene glycol monomethyl ether acetate, or a mixed solvent of diethylene glycol ethyl methyl ether and propylene glycol monomethyl ether acetate.
[0247] Furthermore, as the solvent, an organic solvent having a boiling point of 180 to 250° C. (high boiling point solvent) can also be used, if necessary. The photosensitive composition may contain one type of solvent alone, or may contain two or more types of solvents.
[0248] When the photosensitive composition contains a solvent, the total solid content of the photosensitive composition is preferably from 5 to 80 mass %, more preferably from 5 to 40 mass %, and even more preferably from 5 to 30 mass %, based on the total mass of the photosensitive composition.
[0249] When the photosensitive composition contains a solvent, the viscosity of the photosensitive composition at 25°C is, for example, preferably 1 to 50 mPa·s, more preferably 2 to 40 mPa·s, and even more preferably 3 to 30 mPa·s, from the viewpoint of coatability. The viscosity is measured using a viscometer. As the viscometer, for example, a viscometer manufactured by Toki Sangyo Co., Ltd. (product name: VISCOMETER TV-22) can be suitably used. However, the viscometer is not limited to the above-mentioned viscometer.
[0250] When the photosensitive composition contains a solvent, the surface tension of the photosensitive composition at 25°C is, for example, preferably 5 to 100 mN / m, more preferably 10 to 80 mN / m, and even more preferably 15 to 40 mN / m, from the viewpoint of coatability. The surface tension is measured using a surface tensiometer. As the surface tensiometer, for example, a surface tensiometer manufactured by Kyowa Interface Science Co., Ltd. (product name: Automatic Surface Tensiometer CBVP-Z) can be suitably used. However, the surface tensiometer is not limited to the above-mentioned surface tensiometer.
[0251] Examples of methods for applying the photosensitive composition include printing, spraying, roll coating, bar coating, curtain coating, spin coating, and die coating (that is, slit coating).
[0252] Examples of the drying method include natural drying, heat drying, and reduced pressure drying. The above-mentioned methods can be applied alone or in combination. In this disclosure, "drying" means removing at least a portion of the solvent contained in the composition.
[0253] When the transfer film has a protective film, the transfer film can be produced by laminating the protective film to the photosensitive composition layer. The method for attaching the protective film to the photosensitive composition layer is not particularly limited, and any known method can be used. Examples of a device for laminating the protective film to the photosensitive composition layer include known laminators such as a vacuum laminator and an autocut laminator. The laminator is preferably equipped with any heatable roller, such as a rubber roller, and is capable of applying pressure and heat.
[0254] The transfer film of the present invention can be used for various purposes, such as an electrode protective film, an insulating film, a planarizing film, an overcoat film, a hard coat film, a passivation film, a partition wall, a spacer, a microlens, an optical filter, an anti-reflection film, an etching resist, and a plating member. More specific examples include protective films or insulating films for touch panel electrodes, protective films or insulating films for printed wiring boards, protective films or insulating films for TFT substrates, color filters, overcoat films for color filters, etching resists for wiring formation, and sacrificial layers in plating processes.
[0255] [Method for producing laminate] By using the above-mentioned transfer film, the photosensitive composition layer can be transferred to a receiving material. Among them, the method includes a lamination step of contacting the photosensitive composition layer on the temporary support of the transfer film with a substrate having a conductive layer and laminating the photosensitive composition layer to obtain a substrate having a photosensitive composition layer, the substrate having a conductive layer, the photosensitive composition layer, and the temporary support in this order; an exposure step of pattern-exposing the photosensitive composition layer; A developing step of developing the exposed photosensitive composition layer to form a pattern, Furthermore, the method for producing a laminate preferably includes a peeling step of peeling the temporary support from the substrate with the photosensitive composition layer between the laminating step and the exposure step, or between the exposure step and the development step. The steps of the above process will be described in detail below.
[0256] <Lamination process> The lamination process is a process in which the photosensitive composition layer on the temporary support of the transfer film is brought into contact with and laminated to a substrate having a conductive layer to obtain a substrate with a photosensitive composition layer having a substrate, a conductive layer, a photosensitive composition layer, and a temporary support in that order.
[0257] The exposed photosensitive composition layer on the temporary support of the transfer film is brought into contact with and laminated to a substrate having a conductive layer, and the photosensitive composition layer and the temporary support are disposed on the substrate having a conductive layer by this lamination. In the lamination, the conductive layer and the surface of the photosensitive composition layer are pressed together so as to be in contact with each other. In the above embodiment, the pattern obtained after exposure and development can be suitably used as an etching resist when etching the conductive layer. The method of the pressure bonding is not particularly limited, and known transfer methods and lamination methods can be used. Among them, it is preferable to perform the pressure bonding by superposing the surface of the photosensitive composition layer on a substrate having a conductive layer, and applying pressure and heat with a roll or the like. For lamination, a known laminator such as a vacuum laminator or an autocut laminator can be used.
[0258] The substrate having a conductive layer has a conductive layer on a substrate, and may have an optional layer formed thereon, i.e., the substrate having a conductive layer is a conductive substrate having at least a substrate and a conductive layer disposed on the substrate. Examples of the substrate include a resin substrate, a glass substrate, and a semiconductor substrate. A preferred embodiment of the substrate is described, for example, in paragraph 0140 of International Publication No. 2018 / 155193, the contents of which are incorporated herein by reference.
[0259] From the viewpoints of electrical conductivity and fine line formability, the conductive layer is preferably at least one layer selected from the group consisting of a metal layer, a conductive metal oxide layer, a graphene layer, a carbon nanotube layer, and a conductive polymer layer. Furthermore, only one conductive layer may be disposed on the substrate, or two or more conductive layers may be disposed on the substrate. When two or more conductive layers are disposed, it is preferable that the conductive layers are made of different materials. A preferred embodiment of the conductive layer is described, for example, in paragraph 0141 of International Publication No. 2018 / 155193, the contents of which are incorporated herein by reference.
[0260] The substrate having a conductive layer is preferably a substrate having at least one of a transparent electrode and a routed wiring. Such a substrate can be suitably used as a substrate for a touch panel. The transparent electrode can function favorably as a touch panel electrode. The transparent electrode is preferably composed of a metal oxide film such as ITO (indium tin oxide) or IZO (indium zinc oxide), a metal mesh, or a metal thin wire such as silver nanowire. Examples of the thin metal wires include thin wires of silver, copper, etc. Among them, conductive silver materials such as silver mesh and silver nanowires are preferred.
[0261] The material of the lead wiring is preferably a metal. Examples of the metal material for the wiring include gold, silver, copper, molybdenum, aluminum, titanium, chromium, zinc, and manganese, and alloys of two or more of these metal elements. The material for the wiring is preferably copper, molybdenum, aluminum, or titanium, and particularly preferably copper.
[0262] <Exposure process> The exposure step is a step of pattern-exposing the photosensitive composition layer. Here, the term "pattern exposure" refers to a form of exposure in a pattern, that is, exposure in a form in which exposed areas and non-exposed areas exist. The detailed arrangement and specific size of the pattern in the pattern exposure are not particularly limited. The pattern formed by the developing step described below preferably includes a thin line having a width of 20 μm or less, more preferably includes a thin line having a width of 10 μm or less.
[0263] The light source for the pattern exposure can be appropriately selected and used as long as it can irradiate light in a wavelength range (e.g., 365 nm or 405 nm) that can at least cure the photosensitive composition layer. Among them, the dominant wavelength of the exposure light for the pattern exposure is preferably 365 nm. The dominant wavelength is the wavelength with the highest intensity.
[0264] Examples of light sources include various lasers, light-emitting diodes (LEDs), ultra-high pressure mercury lamps, high pressure mercury lamps, and metal halide lamps. The exposure dose is 5 to 200 mJ / cm 2is preferable, and 10 to 200 mJ / cm 2 is more preferred.
[0265] Preferred embodiments of the light source, exposure dose, and exposure method used for exposure are described, for example, in paragraphs
[0146] to
[0147] of WO 2018 / 155193, the contents of which are incorporated herein by reference.
[0266] <Peeling process> The peeling step is a step of peeling off the temporary support from the substrate with the photosensitive composition layer between the laminating step and the exposure step, or between the exposure step and the development step described below. The peeling method is not particularly limited, and a mechanism similar to the cover film peeling mechanism described in paragraphs
[0161] to
[0162] of JP2010-072589A can be used.
[0267] <Developing process> The development step is a step of developing the exposed photosensitive composition layer to form a pattern. The photosensitive composition layer can be developed using a developer. The developer is preferably an alkaline aqueous solution. Examples of alkaline compounds that can be contained in the alkaline aqueous solution include sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, and choline (2-hydroxyethyltrimethylammonium hydroxide).
[0268] Examples of the development method include paddle development, shower development, spin development, and dip development.
[0269] In the present disclosure, a developer that can be suitably used is, for example, the developer described in paragraph
[0194] of WO 2015 / 093271, and a development method that can be suitably used is, for example, the development method described in paragraph
[0195] of WO 2015 / 093271.
[0270] The detailed arrangement and the specific size of the pattern to be formed are not particularly limited, but a pattern that can obtain the conductive thin wire described later is formed. The interval between the patterns is preferably 8 μm or less, more preferably 6 μm or less. The lower limit is not particularly limited, but is often 2 μm or more.
[0271] The pattern (cured film of the photosensitive composition layer) formed by the above procedure is preferably achromatic. * a * b * In the color system, pattern a * The value is preferably -1.0 to 1.0, and the b * The value is preferably in the range of -1.0 to 1.0.
[0272] <Post-exposure process and post-bake process> The method for producing the laminate may include a step of exposing the pattern obtained by the development step (a post-exposure step) and / or a step of heating the pattern (a post-bake step). When both a post-exposure step and a post-bake step are included, it is preferable to carry out the post-bake step after the post-exposure step.
[0273] <Other processes> The method for producing a laminate of the present invention may include any step (other step) other than those described above. For example, there may be mentioned a process for reducing visible light reflectance described in paragraph
[0172] of WO 2019 / 022089, and a process for forming a new conductive layer on an insulating film described in paragraph
[0172] of WO 2019 / 022089, but the process is not limited to these processes.
[0274] The laminate produced by the laminate producing method of the present invention can be applied to various devices. Examples of devices equipped with the laminate include display devices, printed wiring boards, semiconductor packages, input devices, etc., and are preferably touch panels, more preferably capacitive touch panels. The input devices can be applied to display devices such as organic electroluminescence display devices and liquid crystal display devices. When the laminate is applied to a touch panel, the pattern formed from the photosensitive composition layer is preferably used as a protective film for the touch panel electrode. That is, the photosensitive composition layer included in the transfer film is preferably used to form a protective film for the touch panel electrode. The touch panel electrode includes not only the sensor electrode of the touch sensor but also the lead wiring.
[0275] [Blocked isocyanate compound represented by formula QA] The blocked isocyanate compound of the present invention is a blocked isocyanate compound represented by the following formula QA, and is a blocked isocyanate compound having a novel structure. B 1a -A 1a -L 1a -A 2a -B 2a QA
[0276] B in the formula QA 1a , A 1a , L 1a , A 2a and B. 2a The definitions and preferred embodiments of are as described above, and therefore the explanation thereof will be omitted.
[0277] The compound represented by the formula QA is, for example, a compound having an isocyanate group (e.g., B 1a and B. 2a is an isocyanate group) with the above-mentioned blocking agent. The reaction conditions for the compound having an isocyanate group and the blocking agent are not particularly limited, and the same reaction conditions as those for known blocked isocyanate compounds can be adopted.
[0278] The blocked isocyanate compound represented by the formula QA is preferably a blocked isocyanate compound represented by the formula Q-1.
[0279] [ka] Formula Q-1
[0280] The blocked isocyanate compound represented by formula Q-1 may be an isomer mixture of cis and trans isomers (hereinafter also referred to as a "cis-trans isomer mixture"). When the blocked isocyanate compound represented by formula Q-1 is a cis-trans isomer mixture, the mass ratio of the cis isomer to the trans isomer is preferably cis / trans=10 / 90 to 90 / 10, and more preferably cis / trans=40 / 60 to 60 / 40.
[0281] The use of the compound represented by formula QA is not particularly limited, but it is particularly suitable as a component for forming the photosensitive composition layer in the above-mentioned transfer film.
[0282] [Example of a touch panel] FIG. 1 is a schematic cross-sectional view of a touch panel 90 which is a first specific example of a touch panel to which the transfer film of the present invention can be applied. As shown in FIG. 1, the touch panel 90 has an image display area 74 and an image non-display area 75 (that is, a frame portion). The touch panel 90 also includes touch panel electrodes on both sides of the substrate 32. In particular, the touch panel 90 includes a first metal conductive material 70 on one side of the substrate 32, and a second metal conductive material 72 on the other side. In the touch panel 90, the lead wiring 56 is connected to each of the first metal conductive material 70 and the second metal conductive material 72. The lead wiring 56 may be, for example, a copper wiring or a silver wiring. In the touch panel 90, a metal conductive material protective film 18 is formed on one side of the substrate 32 so as to cover the first transparent electrode pattern 70 and the wiring 56, and a metal conductive material protective film 18 is formed on the other side of the substrate 32 so as to cover the second metal conductive material 72 and the wiring 56. A refractive index adjustment layer may be formed on one surface of the substrate 32.
[0283] FIG. 2 is a schematic cross-sectional view of a touch panel 90 which is a second specific example of a touch panel to which the transfer film of the present invention can be applied. As shown in FIG. 2, the touch panel 90 has an image display area 74 and an image non-display area 75 (that is, a frame portion). The touch panel 90 also includes touch panel electrodes on both sides of the substrate 32. In particular, the touch panel 90 includes a first metal conductive material 70 on one side of the substrate 32, and a second metal conductive material 72 on the other side. In the touch panel 90, the first metal conductive material 70 and the second metal conductive material 72 are each connected to a lead wiring 56. The lead wiring 56 may be, for example, a copper wiring or a silver wiring. The lead wiring 56 is formed inside the metal conductive material protective film 18 and surrounded by the first metal conductive material 70 or the second metal conductive material 72. In the touch panel 90, a metal conductive material protective film 18 is formed on one side of the substrate 32 so as to cover the first transparent electrode pattern 70 and the wiring 56, and a metal conductive material protective film 18 is formed on the other side of the substrate 32 so as to cover the second metal conductive material 72 and the wiring 56. A refractive index adjustment layer may be formed on one surface of the substrate 32. The metal conductive material protective film 18 is preferably a photosensitive composition layer or a cured film of a photosensitive composition layer in the present invention.
[0284] Still another embodiment of the touch panel will be described with reference to FIGS. FIG. 3 is a schematic plan view showing still another specific example of the touch panel, and FIG. 4 is a cross-sectional view taken along line AA in FIG. 3 and 4 show a transparent laminate 200 having, in this order, a transparent electrode pattern (including a first island-shaped electrode portion, a first wiring portion 116, a second island-shaped electrode portion, and a bridge wiring 118), a protective layer 130, and an overcoat layer 132 on a transparent film substrate 124. At least one of the protective layer 130 and the overcoat layer 132 is preferably a photosensitive composition layer or a cured film of a photosensitive composition layer in the present invention.
[0285] Furthermore, as shown in Figures 3 and 4, a through hole 120 is formed in the protective layer 130 located above the second island-shaped electrode portion 114 in the transparent electrode pattern on the transparent film substrate 124, for connecting the second island-shaped electrode portion 114 to a bridge wiring (second wiring portion) 118 for bridging between two adjacent second island-shaped electrode portions 114 and electrically connecting the second island-shaped electrode portions 114 to each other.
[0286] The transparent laminate 200 has, on a transparent substrate 124, a first electrode pattern 134 and a second electrode pattern 136 that extend in the direction of arrow P or the direction of arrow Q, which intersect with each other. Although only a portion of the touch panel is shown in Figures 3 and 4, a first electrode pattern 134 is arranged in one direction (first direction) over a wide area of the transparent substrate, and a second electrode pattern 136 is arranged in a direction (second direction) different from the first direction over a wide area of the transparent substrate.
[0287] 3, the first electrode pattern 134 has a plurality of rectangular electrode portions (first island-shaped electrode portions) 112 arranged in an island shape at equal intervals along the direction of the arrow P on the transparent substrate 124, and adjacent first island-shaped electrode portions 112 are connected and joined together by a first wiring portion 116. This forms an elongated electrode in one direction on the surface of the transparent substrate. The first wiring portion is preferably made of the same material as the first island-shaped electrode portion.
[0288] In addition, in the second electrode pattern 136, in FIG. 3, rectangular electrode portions (second island-shaped electrode portions) 114 that are substantially similar to the first island-shaped electrode portions are arranged in an island shape at equal intervals on a transparent substrate 124 along the direction of arrow Q that is substantially perpendicular to the direction of arrow P, and adjacent second island-shaped electrode portions 114 are connected and continuous by second wiring portions (bridge wiring) 118. As a result, an elongated electrode is formed in a direction different from the first electrode pattern on the surface of the transparent substrate.
[0289] As shown in FIGS. 3 and 4, the first electrode pattern 134 and the second electrode pattern 136 form a bridge structure in which one of the intersecting electrodes jumps over the other at the intersecting portion, so that they are not electrically connected to each other.
[0290] In the touch panel shown in FIG. 4, the protective layer 130 is disposed so as to cover the first electrode pattern 34 and the second electrode pattern 136. EXAMPLES
[0291] The present invention will be described in more detail below with reference to examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of this disclosure. Therefore, the scope of the present invention is not limited to the specific examples shown below. In addition, unless otherwise specified, "parts" and "%" are based on mass. In the following examples, the weight average molecular weight of the resin is the weight average molecular weight determined by gel permeation chromatography (GPC) in terms of polystyrene, and the acid value is the theoretical acid value.
[0292] <Synthesis of alkali-soluble resin P-1> 82.4g of propylene glycol monomethyl ether was charged into a flask and heated to 90°C under a nitrogen stream. A solution of 38.4g of styrene, 30.1g of dicyclopentanyl methacrylate, and 34.0g of methacrylic acid dissolved in 20g of propylene glycol monomethyl ether, and a solution of 5.4g of polymerization initiator V-601 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) dissolved in 43.6g of propylene glycol monomethyl ether acetate were simultaneously dropped into this liquid over a period of 3 hours. After the dropwise addition was completed, 0.75g of V-601 was added three times at 1-hour intervals. The reaction was then continued for another 3 hours. The mixture was then diluted with 58.4g of propylene glycol monomethyl ether acetate and 11.7g of propylene glycol monomethyl ether. The reaction liquid was heated to 100°C under an air stream, and 0.53g of tetraethylammonium bromide and 0.26g of p-methoxyphenol were added. 25.5 g of glycidyl methacrylate (Blenmer GH manufactured by NOF Corp.) was added dropwise over 20 minutes. This was reacted at 100°C for 7 hours to obtain a solution of alkali-soluble resin P-1. The solid content concentration of the obtained solution was 36.5%. In the alkali-soluble resin P-1, the weight average molecular weight in terms of standard polystyrene measured by GPC was 17000, the dispersity was 2.4, and the acid value was 94.5 mgKOH / g. The amount of residual monomer measured by gas chromatography was less than 0.1% by mass relative to the polymer solid content for each monomer.
[0293] <Synthesis of alkali-soluble resins P-2 to P-19> Alkali-soluble resins P-2 to P-19 were synthesized in the same manner as for the synthesis of alkali-soluble resin P-1, except that the type of monomer for obtaining each structural unit contained in the alkali-soluble resin and the content of each structural unit were changed as shown in Table 1. All alkali-soluble resins were synthesized as polymer solutions, and the amount of diluent (propylene glycol monomethyl ether acetate (PGMEA)) was adjusted so that the concentration (solid content concentration) of the alkali-soluble resin in the polymer solution was 36.3 mass%. In Table 1, structural units other than those having a radically polymerizable group are shown by the abbreviation of the monomer for forming each structural unit. The structural units having a radical polymerizable group are shown in the form of an addition structure between monomers. For example, MAA-GMA means a structural unit in which glycidyl methacrylate is added to a structural unit derived from methacrylic acid.
[0294] In Table 1, the abbreviations have the following meanings: St: Styrene (Wako Pure Chemical Industries, Ltd.) VN: Vinylnaphthalene (Wako Pure Chemical Industries, Ltd.) AMS: α-methylstyrene (Tokyo Chemical Industry Co., Ltd.) DCPMA: dicyclopentanyl methacrylate (Tg: 175°C, Fancryl FA-513M, Hitachi Chemical Co., Ltd.) IBXMA: Isobornyl methacrylate (Tg: 173°C, Light Ester IB-X, Kyoeisha Chemical Co., Ltd.) ADMA: 1-adamantyl methacrylate (Tg: 250°C, Adamantate AM (Idemitsu Kosan Co., Ltd.)) CHMA: Cyclohexyl methacrylate (Tg=66°C, CHMA, manufactured by Mitsubishi Gas Chemical Co., Inc.) MAA-GMA: A structural unit in which glycidyl methacrylate is added to a structural unit derived from methacrylic acid. MAA-M100: A structural unit in which CYM-M100 (manufactured by Daicel Corporation; 3,4-epoxycyclohexylmethyl methacrylate) is added to a structural unit derived from methacrylic acid. MAA: Methacrylic acid (Wako Pure Chemical Industries, Ltd.) AA: Acrylic acid (Wako Pure Chemical Industries, Ltd.) MMA: Methyl methacrylate (Wako Pure Chemical Industries, Ltd.) nBMA: normal butyl methacrylate (manufactured by Wako Pure Chemical Industries, Ltd.) HEMA: Hydroxyethyl methacrylate (Wako Pure Chemical Industries, Ltd.) 4HBA: 4-hydroxybutyl acrylate (Wako Pure Chemical Industries, Ltd.)
[0295] [Table 1]
[0296] <Synthesis of blocked isocyanate compound Q-1> Under a nitrogen stream, 453 g of butanone oxime (Idemitsu Kosan Co., Ltd.) was dissolved in 700 g of methyl ethyl ketone. Under ice cooling, 500 g of 1,3-bis(isocyanatomethyl)cyclohexane (cis, trans isomer mixture, Mitsui Chemicals Co., Ltd., Takenate 600) was added dropwise over 1 hour, and the mixture was allowed to react for another 1 hour. The mixture was then heated to 40°C and allowed to react for 1 hour. 1 Completion of the reaction was confirmed by H-NMR (Nuclear Magnetic Resonance) and HPLC (High Performance Liquid Chromatography), and a methyl ethyl ketone solution of a blocked isocyanate compound Q-1 (see the following formula) was obtained.
[0297] <Synthesis of blocked isocyanate compound Q-1-A> A methyl ethyl ketone solution of a blocked isocyanate compound Q-1-A was obtained by referring to the synthesis of the blocked isocyanate compound Q-1. The amount of butanone oxime in the solution was 0.3 parts by mass relative to 100 parts by mass of Q-1-A.
[0298] <Synthesis of blocked isocyanate compound Q-1-B> A methyl ethyl ketone solution of a blocked isocyanate compound Q-1-B was obtained by referring to the synthesis of the blocked isocyanate compound Q-1-A. The amount of butanone oxime in the solution was 1.2 parts by mass per 100 parts by mass of Q-1-B.
[0299] <Synthesis of blocked isocyanate compounds Q-2 to Q-8> Methyl ethyl ketone solutions of blocked isocyanate compounds Q-2 to Q-8 (see the following formula) were obtained by referring to the synthesis method of blocked isocyanate compound Q-1. Note that blocked isocyanate compound Q-6 is a 1:1 (mass ratio) mixture of isomers.
[0300] [ka]
[0301] The NCO values of the blocked isocyanate compounds Q-1 to Q-8 were measured according to the method described above.
[0302] <Preparation of Photosensitive Composition> Photosensitive compositions A-1 to A-38 and A'-1 were prepared with the compositions shown in Table 2 below. In Table 2, the numerical value of each component indicates the content (solid content mass) of each component, and coating solutions of the photosensitive compositions were prepared by adding methyl ethyl ketone and 1-methoxy-2-propyl acetate appropriately so that the content of methyl ethyl ketone in the solvent was 60 mass%, the solid content concentration was 25 mass% for A-1 to A-31, and the solid content concentration was 20 mass% for A-32 to A-38.
[0303] [Table 2]
[0304] [Table 3]
[0305] [Table 4]
[0306] [Table 5]
[0307] [Table 6]
[0308] [Table 7]
[0309] <Preparation of Coating Solution for Forming Refractive Index Adjusting Layer> Next, a coating liquid B-1 for forming a refractive index adjusting layer was prepared according to the composition shown in the following Table 3. The numerical values in Table 3 indicate "parts by mass."
[0310] [Table 8]
[0311] <Preparation of transfer films of Examples 1 to 45 and Comparative Example 1> Any one of the photosensitive compositions A-1 to A-38 and A'-1 was applied to a temporary support, Lumirror 16KS40 (thickness 16 μm, manufactured by Toray Industries, Inc., polyethylene terephthalate film), using a slit nozzle, and then the solvent was evaporated in a drying zone at 100° C. to form a photosensitive composition layer on the temporary support. The amount of the photosensitive composition applied was adjusted so that the thickness of the photosensitive composition layer was as shown in Table 4. Next, a protective film (Lumirror 16KS40 (manufactured by Toray Industries, Inc.)) was pressed onto the photosensitive composition layer to prepare the transfer films of Examples 1 to 45 and Comparative Example 1.
[0312] <Manufacture of Laminate> A cycloolefin resin film with a thickness of 38 μm and a refractive index of 1.53 was subjected to a corona discharge treatment for 3 seconds using a high-frequency oscillator under the following conditions: output voltage 100%, output power 250 W, wire electrode with a diameter of 1.2 mm, electrode length 240 mm, and work electrode distance 1.5 mm, to perform surface modification. The obtained film was used as a transparent substrate. Next, the material C shown in Table 4 below was applied onto a transparent substrate using a slit nozzle, and then irradiated with ultraviolet light (accumulated light amount 300 mJ / cm 2 ) and dried at about 110°C to form a transparent film with a refractive index of 1.60 and a thickness of 80 nm.
[0313] [Table 9]
[0314] [ka]
[0315] The film with the transparent film formed on the transparent substrate was introduced into a vacuum chamber, and an ITO (indium tin oxide) target with a SnO2 content of 10 mass% (indium:tin = 95:5 (molar ratio)) was used to form an ITO thin film with a thickness of 40 nm and a refractive index of 1.82 on the transparent film by direct current (DC) magnetron sputtering (conditions: transparent substrate temperature 150°C, argon pressure 0.13 Pa, oxygen pressure 0.01 Pa). The surface resistance of the ITO thin film was 80 Ω / □ (Ω per square). Next, the ITO thin film was etched and patterned by a known chemical etching method to obtain a conductive substrate having a transparent film and a transparent electrode portion on the transparent substrate.
[0316] The protective film of each transfer film in the Examples and Comparative Examples was peeled off, and the exposed surface of the photosensitive composition was brought into contact with the transparent electrode portion of the conductive substrate, and the photosensitive composition layer was laminated (bonded) so as to cover the transparent electrode portion, thereby forming a laminate in which the photosensitive composition layer and temporary support were disposed on the conductive substrate. The lamination was performed using a vacuum laminator manufactured by MCK Corporation under conditions of a transparent substrate temperature of 40° C., a rubber roller temperature of 100° C., a linear pressure of 3 N / cm, and a conveying speed of 2 m / min.
[0317] Thereafter, a proximity type exposure machine (manufactured by Hitachi High-Tech Electronics Engineering Co., Ltd.) having an ultra-high pressure mercury lamp was used to bring the exposure mask (a quartz exposure mask having a pattern for forming an overcoat) into close contact with the temporary support, and the exposure dose was 120 mJ / cm 2 through the temporary support. 2 (Measured value for i-line) The exposure light had a dominant wavelength of 365 nm.
[0318] The exposed sample was left to stand for 48 hours in a 23°C, 55% humidity environment, and then the temporary support was peeled off and the sample was developed for 60 seconds in a 1% aqueous solution of sodium carbonate at 32°C. After that, the developed transparent substrate was sprayed with ultrapure water from an ultrahigh pressure cleaning nozzle to remove residues. Air was then blown onto the transparent substrate to remove moisture. Next, the obtained pattern was exposed to light at a dose of 400 mJ / cm using a post exposure machine equipped with a high-pressure mercury lamp (manufactured by Ushio Electric Co., Ltd.). 2 (measured value at i-line) (post-exposure). Thereafter, a post-baking treatment was carried out at 145° C. for 30 minutes to form a laminate having a transparent film, a transparent electrode portion, and a pattern (cured film of the photosensitive composition layer) in this order on the transparent substrate.
[0319] <Corrosivity evaluation> Using the transfer films of each Example and Comparative Example from which the protective film had been peeled off, a film having a transparent film and a transparent electrode portion formed on a transparent substrate was transferred onto a PET (polyethylene terephthalate) film (manufactured by Geomatec Co., Ltd.) on which copper foil (substitute for an electrode of a capacitive input device) had been laminated, in the same manner as described above, the exposed surface of the photosensitive composition was brought into contact with the copper foil on the PET film, and the photosensitive composition layer was laminated (bonded together) so as to cover the copper foil, and post-processing (peeling of the temporary support, exposure, development, post-baking, etc.) was carried out to obtain a sample (laminate) having, in this order, the copper foil and a pattern (cured film of the photosensitive composition layer) on the PET film. A 5 cm thick layer of salt water with a concentration of 50 g / L was applied to the surface of the sample pattern. 3 Drop, 50cm 2 After spreading the sample evenly, the moisture was evaporated at room temperature and the sample was left for 32 hours in a 110°C, 85% humidity environment using a HAST tester EHS-221MD (manufactured by Espec Corporation). After that, the salt water was wiped off and the surface condition of the sample was observed and evaluated according to the following criteria. AA, A, B, and C are practically necessary levels, with AA being preferable. (Evaluation Criteria) AA: No copper discoloration at all A: There is slight copper discoloration in some areas. B: There is some slight copper discoloration in some areas. C: A faint copper discoloration is observed over the entire surface. D: Copper discoloration is evident over the entire surface.
[0320] <Evaluation of development residue> The developed and removed portion of the above-mentioned laminate was observed visually and with an optical microscope (20x objective). A and B are practical levels, with A being preferable. (Evaluation Criteria) A: No residues are visible even when observed with an optical microscope. B: Residue is observed in a small area when observed with an optical microscope. C: Residue is clearly visible all over the surface.
[0321] The evaluation results are summarized in Table 5 below.
[0322] [Table 10]
[0323] [Table 11]
[0324] As shown in Table 5, it was shown that the use of a photosensitive composition layer containing an alkali-soluble resin, a polymerizable compound, a polymerization initiator, and a first blocked isocyanate compound can suppress corrosion of wiring (electrodes) (Examples 1 to 45). Comparing Examples 1 to 4 and 6, it was shown that when the first blocked isocyanate compound has a ring structure (Examples 1, 3 and 4), corrosion of the wiring (electrodes) can be further suppressed. Comparing Examples 1, 3 to 5, and 7, it was shown that when the NCO value of the first blocked isocyanate compound was 5.0 mmol / g or more (Examples 1, 3, and 4), corrosion of the wiring (electrodes) could be further suppressed. In comparison between Examples 8 to 10 and 15 to 31, it was shown that when the content of the structural unit derived from a vinylbenzene derivative is 35% by mass or more relative to the total amount of all structural units contained in the alkali-soluble resin (Examples 15 to 31), the corrosion of the wiring (electrodes) can be further suppressed. In particular, it was shown that when the content of the structural unit derived from a vinylbenzene derivative is 45% by mass or more relative to the total amount of all structural units contained in the alkali-soluble resin (Examples 17 to 31), the corrosion of the wiring (electrodes) can be further suppressed. Comparison of Examples 22 to 25 and 32 to 35 shows that when the thickness of the photosensitive composition layer was 3 μm or more (Examples 22 to 25 and 33 to 35), corrosion of the wiring (electrodes) could be further suppressed.
[0325] In contrast, when a photosensitive composition layer not containing a first blocked isocyanate compound was used, it was shown that corrosion of the wiring (electrodes) became significant (Comparative Example 1).
[0326] In preparing the transfer films of the above-mentioned examples and comparative examples, a transfer film having a refractive index adjustment layer corresponding to each of the examples and comparative examples was obtained in the same manner as in preparing the transfer films of the above-mentioned examples and comparative examples, except that a refractive index adjustment layer having a thickness of 80 nm (refractive index: 1.60 or more) was formed by applying coating liquid B-1 for forming a refractive index adjustment layer onto the photosensitive composition layer. The transfer film having the refractive index adjusting layer thus obtained was used to carry out the above-mentioned evaluations, and the evaluation results were similar to those obtained when the transfer films of the Examples and Comparative Examples were used. [Explanation of symbols]
[0327] 18: Metal conductive material protective film 32: Circuit board 56: Wiring 70: First metallic conductive material 72: second metallic conductive material 74: Image display area 75: Image hidden area 90: Touch panel 112:First island electrode part 114:Second island electrode part 116: 1st wiring section 118: Second wiring section (bridge wiring) 120:Through hole 124: Transparent substrate (transparent film substrate) 130: Protective layer 132: Overcoat layer 134: First electrode pattern 136: Second electrode pattern 200: Transparent laminate P: Extension direction of the first electrode pattern Q: Extension direction of the second electrode pattern
Claims
1. A temporary support and a photosensitive composition layer disposed on the temporary support, the photosensitive composition layer contains an alkali-soluble resin, a polymerizable compound, a polymerization initiator, and a blocked isocyanate compound having an NCO value of 4.5 mmol / g or more (excluding Duranate (registered trademark) TPA-B80E); the content of the alkali-soluble resin is 10 to 90% by mass based on the total mass of the photosensitive composition layer, the alkali-soluble resin contains a structural unit having an acid group, and the content of the structural unit having an acid group is 5 to 30 mass% based on the total amount of all structural units contained in the alkali-soluble resin; the acid group is a carboxy group, the content of the blocked isocyanate compound is 1 to 20% by mass based on the total mass of the photosensitive composition layer, The transfer film, wherein the blocked isocyanate compound has a blocked isocyanate group, and the blocked isocyanate group is an isocyanate group blocked with an oxime compound.
2. The transfer film according to claim 1 , wherein the blocked isocyanate compound has an NCO value of more than 5.0 mmol / g.
3. The transfer film according to claim 1 or 2, wherein the blocked isocyanate compound has a ring structure.
4. The transfer film according to any one of claims 1 to 3, wherein the blocked isocyanate compound is a blocked isocyanate compound represented by formula Q. B 1 -A 1 -L 1 -A 2 -B 2 Formula Q In formula Q, B 1 and B 2 each independently represents a blocked isocyanate group; A 1 and A 2 each independently represents a single bond or an alkylene group having 1 to 10 carbon atoms; L 1 represents a divalent linking group.
5. The transfer film according to any one of claims 1 to 4, wherein the blocked isocyanate compound is a blocked isocyanate compound represented by the formula QA. B 1a -A 1a -L 1a -A 2a -B 2a Formula QA In the formula QA, B 1a and B 2a each independently represents a blocked isocyanate group; A 1a and A 2a each independently represents a divalent linking group; L 1a represents a cyclic divalent saturated hydrocarbon group or a divalent aromatic hydrocarbon group.
6. The transfer film according to any one of claims 1 to 5, wherein the photosensitive composition layer further comprises a blocked isocyanate compound having an NCO value of less than 4.5 mmol / g.
7. the alkali-soluble resin contains a structural unit derived from a vinylbenzene derivative, a structural unit having a radical polymerizable group, and a structural unit having the acid group, The transfer film according to any one of claims 1 to 6, wherein the content of the structural unit derived from the vinylbenzene derivative is 35 mass% or more with respect to the total amount of all structural units contained in the alkali-soluble resin.
8. The transfer film according to claim 7 , wherein the content of the structural unit derived from the vinylbenzene derivative is 45 mass % or more based on the total amount of all structural units contained in the alkali-soluble resin.
9. Further comprising a refractive index adjustment layer, the refractive index adjusting layer is disposed in contact with the photosensitive composition layer, The transfer film according to any one of claims 1 to 8, wherein the refractive index adjusting layer has a refractive index of 1.60 or more.
10. The transfer film according to any one of claims 1 to 9, wherein the photosensitive composition layer is used for forming a touch panel electrode protective film.
11. a lamination step of contacting and laminating the photosensitive composition layer on the temporary support of the transfer film according to any one of claims 1 to 10 to a substrate having a conductive layer, thereby obtaining a substrate with a photosensitive composition layer having the substrate, the conductive layer, the photosensitive composition layer, and the temporary support in this order; an exposure step of pattern-exposing the photosensitive composition layer; A developing step of developing the exposed photosensitive composition layer to form a pattern, The method for producing a laminate further comprises a peeling step of peeling the temporary support from the substrate with the photosensitive composition layer between the laminating step and the exposure step, or between the exposure step and the development step.
12. A temporary support and a photosensitive composition layer disposed on the temporary support, the photosensitive composition layer contains an alkali-soluble resin, a polymerizable compound, a polymerization initiator, and a blocked isocyanate compound (excluding Duranate (registered trademark) TPA-B80E); the NCO value of the photosensitive composition layer is greater than 0.50 mmol / g; the content of the alkali-soluble resin is 10 to 90% by mass based on the total mass of the photosensitive composition layer, the alkali-soluble resin contains a structural unit having an acid group, and the content of the structural unit having an acid group is 5 to 30 mass% based on the total amount of all structural units contained in the alkali-soluble resin; the acid group is a carboxy group, the content of the blocked isocyanate compound is 1 to 20% by mass based on the total mass of the photosensitive composition layer, The transfer film, wherein the blocked isocyanate compound has a blocked isocyanate group, and the blocked isocyanate group is an isocyanate group blocked with an oxime compound.
13. The transfer film according to claim 12 , wherein the blocked isocyanate compound has an NCO value of 4.5 mmol / g or more.
14. The transfer film according to claim 12 or 13, wherein the blocked isocyanate compound is a blocked isocyanate compound represented by the formula QA. B 1a -A 1a -L 1a -A 2a -B 2a Formula QA In the formula QA, B 1a and B 2a each independently represents a blocked isocyanate group; A 1a and A 2a each independently represents a divalent linking group; L 1a represents a cyclic divalent saturated hydrocarbon group or a divalent aromatic hydrocarbon group.
15. the alkali-soluble resin contains a structural unit derived from a vinylbenzene derivative, a structural unit having a radical polymerizable group, and a structural unit having the acid group, The transfer film according to any one of claims 12 to 14, wherein the content of the structural unit derived from the vinylbenzene derivative is 35 mass% or more with respect to the total amount of all structural units contained in the alkali-soluble resin.
Citation Information
Patent Citations
JP1975065677A
Photosensitive resin film laminate
JP2020071372A
Photosensitive resin composition, transfer film, protective film for touch panels, touch panel, method for producing touch panel, and image display device
WO2018042833A1
Stacked body, stacked body manufacturing method, and capacitive input device
WO2020066405A1